Minimizing agglomeration, aeration, and preserving the coating of pharmaceutical compositions comprising ibuprofen

By removing the excessive coating material of ibuprofen and adding a protective layer of silicon hydroxide, the problems of drug stability and service life are solved, and the effective anti-polymerization and functional maintenance of the coating material are achieved.

JP2025038069AInactive Publication Date: 2025-03-18CATALENT U K SWINDON ZYDIS LIMITED
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024217675
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-02-22
Filing Date
2024-12-12
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art is difficult to effectively prevent the aggregation of coating materials of ibuprofen, resulting in reduced drug stability and shortened service life.

Method used

The aggregation of the coating material is reduced by removing the excess coating material from ibuprofen and adding silicon hydroxide during the solvent free mixing process to form a protective layer.

Benefits of technology

It effectively prevents the aggregation of ibuprofen coating materials, improves the stability and service life of the medicine, and maintains the integrity of the functional coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025038069000011
    Figure 2025038069000011
  • Figure 2025038069000012
    Figure 2025038069000012
  • Figure 2025038069000013
    Figure 2025038069000013
Patent Text Reader

Abstract

To provide a method that helps minimize agglomeration of coating material for coated Ibuprofen to improve the stability of the pharmaceutical product during storage and to increase its shelf life.SOLUTION: Provided are pharmaceutical compositions and methods for preparing pharmaceutical compositions comprising Ibuprofen using solventless mixing methods. Excess coating material that is not bound to coated Ibuprofen may be removed by a sieving process. Coating and dosing ratios can also be optimized to minimize the amount of excess unbound coating material. Additionally, the compositions can be formulated to preserve the functional coating of coated Ibuprofen and to minimize aeration of Ibuprofen when mixed into suspension.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims priority to U.S. Provisional Application Nos. 62 / 809,307, 62 / 809,287, and 62 / 809,293, each filed on February 22, 2019, the entire contents of each of which are incorporated herein by reference.

[0002] This relates to a process for coating ibuprofen, and more specifically to a process that minimizes excess coating material to prevent clumping of coated ibuprofen in lyophilized oral disintegrating dosage forms during storage, a process that minimizes aeration of pharmaceutical suspensions containing ibuprofen for improved dose weight accuracy while maintaining the integrity of a functional coating on the ibuprofen, and a process that preserves the coating of coated ibuprofen produced by a solvent-free mixing process and formulated to delay the release of ibuprofen upon oral administration. [Background technology]

[0003] A pharmaceutical composition typically contains both an active pharmaceutical ingredient as well as one or more inactive ingredients. An active pharmaceutical ingredient (API) is biologically active and designed to directly affect a patient's symptoms, disease, disorder, and / or illness. An example of an active pharmaceutical ingredient is ibuprofen. On the other hand, the inactive ingredient(s) of a pharmaceutical composition are pharmacologic inactive and may be used for a variety of purposes, including, but not limited to, improving long-term stability, filling or diluting solid formulations, promoting drug absorption, adjusting the viscosity of liquid formulations, improving solubility, and / or aiding in the manufacture of the pharmaceutical composition.

[0004] In addition, some inactive ingredients can be used to mask the taste of APIs such as ibuprofen. Many APIs are known to exhibit unpleasant organoleptic properties such as bitterness, burning, and numbness when dissolved in the oral cavity. For example, some orally administered pharmaceutical compositions are designed to disperse in the mouth to allow administration without water, targeting pediatric patients, geriatric patients, veterinary patients, and / or other types of patients who may have difficulty swallowing. For these types of orally administered pharmaceutical compositions, inactive ingredients can be used to form a "functional coating" to mask the taste of the API, or ibuprofen.

[0005] For example, inactive ingredients may be used to mask the taste of the API by wet or dry coating the API particles to produce a functional coating that surrounds the API particles and prevents release of the API in the mouth. In wet particle coating, the inactive ingredients (polymers and additives) are dissolved or dispersed in a solvent or water to form a suspension or solution. This suspension or solution can then be sprayed onto the surface of the API particles and evaporation of the solvent or water can form a film coating. Examples of techniques for wet particle coating include microencapsulation, fluid bed coating, spray drying, pan coating, etc. In dry particle coating (also called solventless coating), the API particles are physically coated with fine particles of the inactive ingredients (polymers and additives) to form a particle composite. Examples of dry particle coating include hot melt coating, supercritical coating, impaction coating, electrostatic coating. API particles coated with taste-masking inactive ingredients can provide a more pleasant experience for patients who have difficulty swallowing or have sensitivities to tastes that would otherwise result in a negative patient experience and poor compliance.

[0006] Additionally, one type of pharmaceutical composition is an orally disintegrating tablet (ODT), which is a pharmaceutical composition targeted to pediatric patients, geriatric patients, veterinary patients, and / or other types of patients who may have difficulty swallowing.

[0007] To accurately dispense a pharmaceutical composition into small administrable forms, hydrophobically coated API particles can be placed in a matrix solution / suspension to form a pharmaceutical suspension. Mixing to form a pharmaceutical suspension allows for improved dosing accuracy. Often, this pharmaceutical suspension containing hydrophobically coated API particles is dosed into a mold, dried, and the molded article can then be transferred, for example, to a bottle. However, handling such pharmaceutical compositions can increase the risk of damage and contamination.

[0008] Therefore, many API suspensions today are instead dosed into preformed blister packs. Preformed blister packs eliminate one of the handling steps mentioned above. Instead of dosing into a mold and then transferring the molded part to a bottle for packaging, the pharmaceutical suspension can be dosed into a preformed blister pack that the manufacturer can dry and then seal and package. Thus, the preformed blister pack functions as both a mold and a package in which the pharmaceutical composition can be stored. Summary of the Invention [Problem to be solved by the invention]

[0009] Methods are provided for minimizing the agglomeration of coating materials for coated ibuprofen produced using various mixing processes. Agglomeration of coating materials can reduce the stability of a pharmaceutical product over time. For example, the disintegration time of a pharmaceutical product can increase over time when it includes an agglomerated coating material. An increase in disintegration time and / or a decrease in dissolution rate indicates an unstable pharmaceutical product. An unstable pharmaceutical product can result in a shorter than desired storage period. Thus, the provided embodiments help minimize the agglomeration of coating materials for coated ibuprofen, which can improve the stability of the pharmaceutical product during storage and increase its shelf life. [Means for solving the problem]

[0010] For example, the methods described include removing excess coating material from the coated ibuprofen to minimize the possibility of agglomeration of the coating material particles. In particular, the methods provided include sieving the coated ibuprofen so that the final pharmaceutical product is properly surrounded by a dry matrix, minimizing any agglomeration of the coating material particles upon storage. The pharmaceutical compositions described provide disintegration times and dissolution rates that remain relatively stable over time.

[0011] Also provided are compositions and methods for preparing compositions that can minimize aeration of hydrophobic coated ibuprofen in suspension. For example, hydrophobic coated ibuprofen can be mixed into a matrix solution / suspension to form a pharmaceutical suspension that can be accurately dosed into a mold to form a solid pharmaceutical composition (e.g., an article, tablet, etc.) for administration to a patient. However, due to the hydrophobicity of the coated ibuprofen, the coated ibuprofen resists dispersion into the solution / suspension. This can therefore cause air to become entrained with the pharmaceutical suspension, also known as aeration. Entrapped air, or aeration of the pharmaceutical suspension, can cause phase separation of the coated ibuprofen in the pharmaceutical suspension, resulting in a non-homogeneous pharmaceutical suspension. Aeration and non-homogeneous pharmaceutical suspensions can result in poor dose weight accuracy of the pharmaceutical suspension containing hydrophobic ibuprofen administered into a preformed blister pack and poor content uniformity in the finished product (i.e., pharmaceutical composition).

[0012] Conventional anti-aeration and / or mechanical means to minimize aeration have not been found to be successful due to the high viscosity of pharmaceutical suspensions. For example, minimizing aeration can be achieved by applying a vacuum to pharmaceutical suspensions, but depending on the composition and further processing requirements, this approach may not be appropriate. In particular, viscous suspensions "hold" trapped air, so applying a vacuum to pharmaceutical suspensions may cause the suspension to rise. Volatile formulation components may also be lost during vacuum processing. Furthermore, conventional anti-aeration agents such as ethanol or simethicone emulsions are similarly ineffective in preventing suspension aeration.

[0013] Thus, the compositions and methods provided herein minimize aeration of pharmaceutical suspensions containing hydrophobically coated ibuprofen, improve suspension homogeneity, and increase dose weight accuracy. Specifically, provided embodiments can include matrix solutions / suspensions that include chemical compounds that include terpenes and / or terpinols. In some embodiments, the matrix solutions / suspensions can include the terpene limonene. By introducing chemical compounds that include terpenes such as limonene, the hydrophobically coated ibuprofen can be more easily incorporated into the matrix solution / suspension, minimizing overall aeration of the pharmaceutical suspension.

[0014] Also provided herein are pharmaceutical compositions formulated to preserve the functional coating of functionally coated ibuprofen during the manufacturing process, and methods for preparing pharmaceutical compositions. Functionally coated ibuprofen is often mixed to form a pharmaceutical suspension. The pharmaceutical suspension allows for accurate dosing to form an administrable pharmaceutical product. Typically, the shear forces required to incorporate functionally coated ibuprofen into a pharmaceutical suspension can erode the functional coating. This erosion of the coating can destroy or damage the properties of the functional coating. Thus, functionally coated ibuprofen with an eroded coating can experience increased dissolution rate and reduced taste masking properties when orally administered to a patient.

[0015] However, the pharmaceutical compositions and methods for preparing pharmaceutical compositions provided herein include preserving the coating of functionally coated ibuprofen in pharmaceutical suspension with hydrophobic fumed silica. Specifically, the hydrophobic fumed silica can provide a protective layer surrounding and / or embedded within the functionally coated ibuprofen particles. In some embodiments, the solventless process for producing functionally coated ibuprofen can produce ibuprofen comprising a first coating. According to some embodiments, hydrophobic fumed silica can be added during the solventless mixing process to produce a second protective coating surrounding and / or partially or completely embedded within the functionally coated ibuprofen.

[0016] Additionally, the second protective coating may limit interactions between the functionally coated ibuprofen and the matrix solution / suspension, thereby minimizing the impact of the functionally coated ibuprofen on the performance properties of the matrix.

[0017] In some embodiments, the pharmaceutical composition comprises 65-85% w / w ibuprofen, 15-30% w / w of a coating material coating the ibuprofen, and 3-15% w / w of a matrix surrounding the ibuprofen. In some embodiments, the pharmaceutical composition comprises 50-400 mg of ibuprofen. In some embodiments, the coating material comprises a first coating material and a second coating material, and the pharmaceutical composition comprises 10-30% w / w of the first coating material and 0.5-10% w / w of the second coating material. In some embodiments, the first coating material comprises a wax. In some embodiments, the second coating material comprises silica. In some embodiments, the pharmaceutical composition comprises 1-5% w / w of an anti-breathing agent. In some embodiments, the first coating material comprises one or more of carnauba wax, synthetic wax, or candelilla wax. In some embodiments, the matrix comprises a matrix former and a structure former. In some embodiments, the matrix forming agent comprises one or more of a water soluble material, a water dispersible material, a polypeptide, a polysaccharide, a polyvinyl alcohol, a polyvinylpyrrolidone, and an acacia. In some embodiments, the matrix forming agent comprises a polypeptide. In some embodiments, the polypeptide comprises gelatin. In some embodiments, the structure forming agent comprises one or more of mannitol, dextrose, lactose, galactose, and a cyclodextrin. In some embodiments, the structure forming agent comprises mannitol. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least one month under storage conditions of at least 25° C. and at least 60% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least two months under storage conditions of at least 25° C. and at least 60% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 3 seconds or less for at least two months under storage conditions of at least 25° C. and at least 60% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least one month under storage conditions of at least 30° C. and at least 65% relative humidity.In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 2 months under storage conditions of at least 30° C. and at least 65% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 1 month under storage conditions of at least 40° C. and at least 75% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 2 months under storage conditions of at least 40° C. and at least 75% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 3 months under storage conditions of at least 25° C. and at least 60% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 3 months under storage conditions of at least 30° C. and at least 65% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 3 months under storage conditions of at least 40° C. and at least 75% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 6 months under storage conditions of at least 25° C. and at least 60% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 6 months under storage conditions of at least 30° C. and at least 65% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 6 months under storage conditions of at least 40° C. and at least 75% relative humidity. In some embodiments, the pharmaceutical composition has a disintegration test result of 10%, 5%, 3% or less after 5 minutes. In some embodiments, the matrix comprises a viscosity modifier. In some embodiments, the viscosity modifier comprises xanthan gum. In some embodiments, the anti-aeration agent comprises one or more of a terpene or a terpinol. In some embodiments, the anti-aeration agent comprises a liquid flavor. In some embodiments, the anti-aeration agent comprises a liquid flavor comprising limonene. In some embodiments, the anti-aeration agent comprises one or more of an orange flavor, a lemon flavor, a grapefruit flavor, a lime flavor, a strawberry flavor, or a peppermint flavor.In some embodiments, the pharmaceutical composition comprises 3-10% w / w matrix forming agent.In some embodiments, the pharmaceutical composition comprises 3-10% w / w structure forming agent.

[0018] In some embodiments, the pharmaceutical composition may be prepared by a process comprising: coating ibuprofen with a first coating material to form a coated ibuprofen, the first coating material comprising one or more deformable components; applying a mechanical stress to the coated ibuprofen to deform the one or more deformable components; coating the coated ibuprofen with a second coating material comprising silica, applying a mechanical stress to embed the second coating material into the first coating material of the coated ibuprofen; sieving the coated ibuprofen to remove excess first coating material, the excess first coating material comprising first coating material not bound to the coated ibuprofen; forming a pharmaceutical suspension comprising twice coated ibuprofen and a matrix solution or suspension; administering the pharmaceutical suspension into a mold; and freeze-drying the administered pharmaceutical suspension in the mold to form a pharmaceutical composition. In some embodiments, sieving the coated ibuprofen comprises passing the coated ibuprofen through a device comprising two or more sieves. In some embodiments, sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 75 μm or greater. In some embodiments, sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 200 μm or less. In some embodiments, the weight of the administered pharmaceutical suspension is within 10 percent of the target dose weight. In some embodiments, the weight of the administered pharmaceutical suspension has a consistency within 5 percent of the target dose weight. In some embodiments, the weight of the administered pharmaceutical suspension has a consistency within 2.5 percent of the target dose weight. In some embodiments, the weight of the administered pharmaceutical suspension has a consistency within 1 percent of the target dose weight.In some embodiments, mixing the coated ibuprofen into the matrix solution or suspension comprises in-line mixing at 15-20 degrees Celsius. In some embodiments, the coated ibuprofen experiences less than 40% loss in particle size within the first 2 hours after mixing into the solution matrix. In some embodiments, the coated ibuprofen experiences less than 30% loss in particle size within the first 2 hours after mixing into the solution matrix. In some embodiments, the coated ibuprofen experiences less than 20% loss in particle size within the first 2 hours after mixing into the solution matrix.

[0019] In some embodiments, the method of treating a patient comprises administering to the patient any of the pharmaceutical compositions disclosed herein. In some embodiments, the patient is a human.

[0020] In some embodiments, a method of preparing a pharmaceutical composition includes coating ibuprofen with a first coating material to form a coated ibuprofen, the first coating material comprising one or more deformable components; applying a mechanical stress to the coated ibuprofen to deform the one or more deformable components; coating the coated ibuprofen with a second coating material comprising silica, applying a mechanical stress to embed the second coating material into the first coating material of the coated ibuprofen; sieving the coated ibuprofen to remove excess first coating material, the excess first coating material comprising first coating material not bound to the coated ibuprofen; forming a pharmaceutical suspension comprising twice coated ibuprofen and a matrix solution or suspension; administering the pharmaceutical suspension into a mold; and lyophilizing the administered pharmaceutical suspension in the mold to form a pharmaceutical composition.

[0021] The invention will now be described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]

[0022] [Figure 1A] 1 shows API particles coated with particles of a deformable coating material (i.e., a first coating layer), according to some embodiments. [Figure 1B] 1 shows API particles coated with a continuous film layer (i.e., a first coating layer) of a deformable coating material, according to some embodiments. [Figure 1C] 1 shows API particles coated with a continuous film layer of a deformable coating material (i.e., a first coating layer) with silica particles partially embedded and / or embedded on the surface of the first coating layer (i.e., a second coating layer), according to some embodiments. [Diagram 2] 1 shows a scanning electron microscope (SEM) image of uncoated API particles, according to some embodiments. [Diagram 3] 1 shows an SEM image of coated API particles, according to some embodiments. [Figure 4A] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4B] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4C] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4D] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4E] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4F]1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4G] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4H] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4I] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Figure 4J] 1 is a series of photomicrographs taken of sieved coated ibuprofen of Examples 1-4. [Diagram 5] 1 is a graph providing an assessment of d10 particle size of functionally coated ibuprofen with different concentrations of a second protective coating of silica according to some embodiments. [Figure 6] 1 shows a graph providing an assessment of d50 particle size of functionally coated ibuprofen with different concentrations of a second protective coating of silica according to some embodiments. [Figure 7] 1 shows a graph providing an assessment of d90 particle size of functionally coated ibuprofen with different concentrations of a second protective coating of silica according to some embodiments. [Figure 8] 1 shows a graph of low volume dissolution of ibuprofen coated with carnauba wax having various levels of hydrophobic fumed silica, according to some embodiments. [Figure 9] 1 shows a graph of low volume dissolution of ibuprofen coated with Sasol (synthetic) wax containing various levels of hydrophobic fumed silica, according to some embodiments. [Figure 10] 1 shows a graph providing an evaluation of d10 particle size of hydrophobically coated ibuprofen with various concentrations of liquid flavor. [Figure 11]1 shows a graph providing an evaluation of d50 particle size of hydrophobically coated ibuprofen with various concentrations of liquid flavor. [Figure 12] 1 shows a graph providing an evaluation of d90 particle size of hydrophobically coated ibuprofen with various concentrations of liquid flavor. [Figure 13] FIG. 1 shows a graph providing an assessment of d10 particle size of hydrophobically coated ibuprofen with various concentrations of pure limonene. [Figure 14] FIG. 1 shows a graph providing an evaluation of d50 particle size of hydrophobically coated ibuprofen with various concentrations of pure limonene. [Figure 15] FIG. 1 shows a graph providing an assessment of d90 particle size of hydrophobically coated ibuprofen with various concentrations of pure limonene. [Figure 16] 1 shows a graph comparing various particle size profiles of hydrophobically coated ibuprofen in strawberry and orange liquid flavors. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] Exemplary embodiments of the method for minimizing and / or preventing the agglomeration of the coating material of coated ibuprofen, the method for preserving the coating of coated ibuprofen, and the method for minimizing the aeration of ibuprofen in pharmaceutical suspension are described herein. Also described are pharmaceutical compositions comprising ibuprofen prepared by any one or more of the disclosed methods. Each of these methods and pharmaceutical compositions is described in detail below. Pharmaceutical compositions comprising ibuprofen can be prepared using any combination of features from the preparation methods described below.

[0024] 1A, 1B, and 1C show different phases of a coated API particle (e.g., ibuprofen) according to some embodiments. In some embodiments, the API particle can be combined with one or more coating materials to produce a coated API. The coating can include materials including water-soluble and / or water-swellable materials as well as water-insoluble materials (described in more detail below).

[0025] For example, FIG. 1A shows an API particle 102 surrounded by particles of a coating material 104. To achieve the coated API particle of FIG. 1A, the combined API (i.e., API particle 102) and one or more coating material(s) (i.e., coating material particles 104) may be exposed to mechanical and / or thermal energy to produce an ordered mixture of API particles 102 including discrete layers of coating material particles 104 that stratify the surface of the API particle 102. The API particle 102 of FIG. 1A is shown with a single layer of discrete particles of the coating material(s). However, the API particle 102 may have two or more discrete layers of coating particles. Additionally, FIG. 2 shows an SEM image of an uncoated API particle.

[0026] FIG. 1B shows API particles 102 surrounded by a continuous deformable film layer 104. Specifically, FIG. 1B shows that all of the coating material particles 104 may be deformable and may deform when subjected to mechanical stress and / or high temperature. Thus, since all coating materials include deformable properties, the coating material 104 of FIG. 1B is a relatively smooth and continuous coating layer after exposure to mechanical and / or thermal energy. In some embodiments, the API particles 102 may have two or more relatively smooth and continuous coating layers. As used herein, a "continuous film" may be a layer surrounding the API particles formed by melting / softening or otherwise decomposing one or more deformable components of individual coating material particles to include a single continuous layer surrounding the API particles. FIG. 3 also provides an SEM image showing coated API particles, according to some embodiments.

[0027] In some embodiments, one or more of the coating materials may not be deformable but may be embedded in the deformable coating layer. Thus, the continuous film may include solid particles of non-deformed material embedded in the deformed coating material. FIG. 1C shows that the continuous film 104 may include one or more solid non-deformed particles 108 of non-deformed material partially embedded and / or embedded in the deformed coating material of the continuous film 104. This continuous film 104 of FIG. 1B or 1C may ensure a coating (e.g., a coating that masks the taste of the API) and delayed API release. In some embodiments, the API particles 102 may have two or more continuous coating layers partially embedded and / or embedded with the non-deformed coating material particles. FIG. 3 also provides an SEM image showing functionally coated API particles according to some embodiments.

[0028] As used herein, the terms "deformable," "deformable component," "deformable component of a coating material," and other related terms refer to one or more components of a water-soluble, water-swellable, and / or water-insoluble material that may degrade when subjected to mechanical stress and / or elevated temperatures.

[0029] In some embodiments, the coated API particles may comprise ibuprofen. In some embodiments, the coated API particles or pharmaceutical compositions may comprise 30.0-90.0% w / w ibuprofen. In some embodiments, the coated API particles or pharmaceutical compositions may comprise 40.0-85.0% w / w, 50.0-80.0% w / w, or 70.0-80.0% w / w ibuprofen. In some embodiments, the coated API particles or pharmaceutical compositions may comprise greater than 40.0% w / w, greater than 50.0% w / w, greater than 60.0% w / w, greater than 65% w / w, greater than 70.0% w / w, greater than 75.0% w / w, greater than 80.0% w / w, or greater than 85.0% w / w ibuprofen. In some embodiments, the coated API particles or pharmaceutical compositions may comprise less than 90.0% w / w, less than 85.0% w / w, less than 80.0% w / w, less than 75.0% w / w, less than 70.0% w / w, less than 60.0% w / w, less than 50.0% w / w, or less than 40.0% w / w of ibuprofen.

[0030] The coating 104 surrounding the API particles 102 may include materials including water soluble and / or water swellable materials and water insoluble materials. In some embodiments, the coating may directly coat the API particles (e.g., ibuprofen) or may coat API particles that already include one or more coatings. In some embodiments, the ratio of coating material to API may be optimized to minimize excess coating material. For example, the coating material may include 5-85% w / w, 10-50%, 15-30% of the API and coating material mixture or pharmaceutical composition. In some embodiments, the coating material may include less than 85%, less than 80%, less than 75%, less than 70%, less than 65%, less than 60%, less than 55%, less than 50%, less than 45%, less than 40%, less than 35%, less than 30%, less than 25%, less than 20%, less than 15%, or less than 10% of the API and coating material mixture or pharmaceutical composition. In some embodiments, the coating material may comprise more than 5%, more than 10%, more than 15%, more than 20%, more than 25%, more than 30%, more than 35%, more than 40%, more than 45%, more than 50%, more than 55%, more than 60%, more than 65%, more than 70%, or more than 75% of the mixture or pharmaceutical composition of API and coating material, In some embodiments, the percentage of coating material may include two or more layers of coating material.

[0031] The water-swellable material of the coating material may be particles with a median particle size of about 0.5 μm to about 20 μm or about 1 μm to about 10 μm. In some embodiments, the water-swellable material may be approximately 10 times smaller than ibuprofen to allow for regular mixing and coating. The water-swellable material may expand upon absorption of water such that the diameter of the water-swellable particles increases by at least about 120 to 600%. The coating material or pharmaceutical composition may comprise 0 to 8% w / w or 0.1 to 0.9% w / w of the water-swellable material. In some embodiments, the coating material or pharmaceutical composition may comprise 0.5 to 6.0% w / w, 1.0 to 4.0% w / w, 1.5 to 3.5% w / w, or 2.0 to 3.0% w / w of the water-swellable material. In some embodiments, the coating material or pharmaceutical composition may contain less than 8.0% w / w, less than 6.0% w / w, less than 4.0% w / w, less than 2.0% w / w, less than 1.0% w / w, or less than 0.5% w / w of water-swellable material. In some embodiments, the coating material or pharmaceutical composition may contain more than 0.1% w / w, more than 0.5% w / w, more than 1.0% w / w, more than 2.0% w / w, more than 3.0 w / w%, more than 5.0% w / w, or more than 6.0% w / w of water-swellable material. The water-swellable material of the coating material may be deformable under mechanical stress and / or elevated temperature (described in detail below). The water-swellable material may be any one or more of crospovidone, croscarmellose, sodium starch glycolate, or any other suitable disintegrant used in the pharmaceutical industry as an additive or blend made for tableting.

[0032] The water-soluble material of the coating material may be particles having a median particle size of about 0.5 μm to about 20 μm or about 1 μm to about 10 μm. In some embodiments, the water-soluble material may be approximately 10 times smaller than ibuprofen to allow for orderly mixing and coating. The water-soluble material may have a water solubility of at least about 50 mg / mL in water at neutral pH and 20° C. Additionally, the water-soluble material may have a water solubility of about 3 to 60 μg / m 2The coating material may have an intrinsic dissolution rate of 0.5-25% w / w, 1.0-15% w / w, 1.5-10% w / w, or 2.0-3.0% w / w of the water soluble material. The water soluble material of the coating material may be deformable under mechanical and / or thermal energy. The coating material or pharmaceutical composition may comprise 0-35% w / w of the water soluble material. In some embodiments, the coating material or pharmaceutical composition may comprise 0.5-25% w / w, 1.0-15% w / w, 1.5-10% w / w, or 2.0-3.0% w / w of the water soluble material. In some embodiments, the coating material or pharmaceutical composition may comprise less than 35% w / w, less than 30% w / w, less than 25% w / w, less than 20% w / w, less than 15% w / w, less than 10% w / w, less than 5.0% w / w, less than 4.5% w / w, less than 4.0% w / w, less than 3.5% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, less than 1.0% w / w, or less than 0.5% w / w of water soluble material. In some embodiments, the coating material or pharmaceutical composition may comprise more than 0.1% w / w, more than 0.5% w / w, more than 1.0% w / w, more than 1.5% w / w, more than 2.0% w / w, more than 2.5% w / w, more than 3.0% w / w, more than 4.0% w / w, more than 5.0% w / w, more than 8.0% w / w, more than 10% w / w, more than 15% w / w, more than 20% w / w, more than 25% w / w, or more than 30% w / w of a water soluble material. The water soluble material may be one or more of sucrose, mannitol, sorbitol, polyvinylpyrrolidone, hydroxypropylcellulose, lactose, poly-(ethylene oxide), and any other suitable micronizable material or polyol.

[0033] The above 3 to 60 μg / m 2 In addition to the intrinsic dissolution rate of about 60-300 μg / m 2This can allow for the use of water-soluble and / or water-swellable materials with a higher intrinsic dissolution rate of s. However, ibuprofen with a coating material with a higher intrinsic dissolution rate should be dry coated with hydrophobic silica. Dry coated ibuprofen where the coating comprises a water-soluble and / or water-swellable material with a higher intrinsic dissolution rate can increase the disintegration time of ibuprofen, thereby failing to effectively mask the taste of ibuprofen. Therefore, dry coating ibuprofen with silica as a second coating material to slow down the dissolution rate can improve the in vivo taste masking performance of the coating. The coated ibuprofen can comprise 0.5-35% w / w silica. In some embodiments, the coated ibuprofen or pharmaceutical composition can comprise 0.5-20% w / w, 0.5-10% w / w, or 0.5-5% w / w hydrophobic fumed silica. In some embodiments, the coated ibuprofen or pharmaceutical composition can comprise more than 0.5% w / w, more than 1.0% w / w, more than 1.5% w / w, more than 2.0% w / w, more than 2.5% w / w, more than 3.0% w / w, more than 4.0% w / w, more than 5.0% w / w, more than 10% w / w, more than 15% w / w, more than 20% w / w, more than 25% w / w, or more than 30% w / w of hydrophobic fumed silica. In some embodiments, the coated ibuprofen or pharmaceutical composition may comprise less than 35% w / w, less than 25% w / w, less than 15% w / w, less than 10% w / w, less than 5.0% w / w, less than 4.0% w / w, less than 3.5% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, or less than 1.0% w / w of hydrophobic fumed silica.Examples of silica that can be used include, but are not limited to, Aerosil R972 silica (Degussa), CAB-O-SIL EH-5 silica (Cabot), OX-50 silica (Degussa), COSM055 (Catalyst & Chemical Ind. Co. Ltd (Japan)), P-500 hydrophilic silica (Catalyst & Chemical Ind. Co. Ltd (Japan)), and TS5 silica (Cabot). In addition, suitable devices that can be used to dry coat with silica include, but are not limited to, Comil (U3 Quadro Comil of Quadro Pennsylvania, US), LabRAM (Resodyne Minnesota, US), Magnetically Assisted Impact Coater (MAIC, Aveka Minnesota, US), and Fluid Energy Mill (FEM, Qualification Micronizer of Sturtevant Massachusetts US).

[0034] The pharmaceutical composition may be prepared by dosing the pharmaceutical suspension into a preformed blister pack. In some embodiments, a freeze-dried orally disintegrating tablet may be prepared by dosing the suspension into a blister pack. In some embodiments, the dosing pump pumps by volume, but the process is controlled by weight. Thus, to ensure content uniformity from one dosage form to the next, the dosing process may be controlled so that the volume-to-weight percentage of the administered suspension is consistent. For example, the volume-to-weight percentage may be consistent within 10 percent, within 8 percent, within 6 percent, within 5 percent, within 4 percent, within 3 percent, within 2 percent, within 1.5 percent, within 1 percent, within 0.5 percent, or within 0.25 percent. In some embodiments, the weight of the administered pharmaceutical suspension is within 10 percent, within 8 percent, within 6 percent, within 5 percent, within 4 percent, within 2.5 percent, within 2 percent, within 1.5 percent, within 1 percent, within 0.5 percent, or within 0.25 percent of the target weight. Additionally, the viscosity of the pharmaceutical suspension must be kept low enough to facilitate administration: as noted above, highly viscous pharmaceutical suspensions can cause the pump to seize during administration.

[0035] The water-insoluble material of the coating material may also be particles comprising less than an average particle size smaller than that of ibuprofen. For example, the water-insoluble material(s) may comprise an average particle size of about 1-20 μm, about 1-12 μm, about 2-10 μm, about 5-12 μm, or about 5-6 μm. In some embodiments, the water-insoluble material may be approximately 10 times smaller than that of ibuprofen to allow for orderly mixing and coating. The water-insoluble material of the coating material may be deformable under mechanical stress and / or elevated temperature. The coating material or pharmaceutical composition may comprise 5-70% w / w, 10-60% w / w, 10-50% w / w, 10-40% w / w, 10-35% w / w, or 15-30% w / w of the water-insoluble material. In some embodiments, the coating material or pharmaceutical composition may comprise more than 5% w / w, more than 10% w / w, more than 15% w / w, more than 20% w / w, more than 25% w / w, more than 30% w / w, more than 35% w / w, or more than 40% w / w of water insoluble material. In some embodiments, the coating material or pharmaceutical composition may comprise less than 70% w / w, less than 60% w / w, less than 50% w / w, less than 45% w / w, less than 40% w / w, less than 35% w / w, or less than 30% w / w of water insoluble material. Examples of suitable water insoluble materials include, but are not limited to, ethyl cellulose, polyethylene, polypropylene, polytetrafluoroethylene, carnauba wax, candela wax, castor wax, polyamide wax, and / or synthetic waxes.

[0036] In some embodiments, mechanical and / or thermal energy can be used to deform one or more water-insoluble, water-swellable, and / or water-insoluble materials. For example, a PharmaRAM II acoustic mixer, a RAM5 Pharma mixer, or a RAM55 Pharma mixer (Resodyn Mixers) can be used to apply mechanical stress to the functionally coated ibuprofen. The coated ibuprofen can be exposed to up to 100 times the force of gravity (100G acceleration) during this acoustic mixing process. These high forces cause particle-particle collisions that generate energy in the form of heat, which can be used to deform one or more water-insoluble, water-swellable, and / or water-insoluble materials on the API.

[0037] However, the above coating processes may also produce "loose" or "free" coating material particles. Figure 2 is an SEM image of an uncoated API particle. Figure 3 is an SEM image of a coated API particle 312. The "loose" or "free" coating material particles 314 are not bound to the coated API particle 312.

[0038] Once sieved, the coated ibuprofen can be mixed into the matrix solution / suspension to form a pharmaceutical suspension (e.g., coated ibuprofen + matrix solution / suspension) and dosed by weight into pockets of preformed blister packs to form aliquots of pharmaceutical suspension. Once dosed, the blister packs containing the aliquot pharmaceutical suspension are frozen under sub-zero conditions. The administered frozen aliquots of pharmaceutical suspension are kept in a frozen state until ready for lyophilization, during which the solvent of the pharmaceutical suspension is removed to form the pharmaceutical composition.

[0039] The matrix solution / suspension may include a matrix former, a structure former, and a solvent. For example, the matrix former may include any water-soluble or water-dispersible material that is pharmacologically acceptable or inert to the functionally coated ibuprofen. In some embodiments, the matrix former may be a polypeptide, such as gelatin. Gelatin may be at least partially hydrolyzed (by heating in water). Other suitable matrix former materials include, but are not limited to, hydrolyzed dextran, dextrin, and polysaccharides, such as alginate, polyvinyl alcohol, polyvinylpyrrolidone, and / or acacia. In some embodiments, the amount of matrix in the pharmaceutical composition (e.g., orally disintegrating tablet) may be 1-30% w / w. In some embodiments, the amount of matrix may be less than 30% w / w, less than 25% w / w, less than 20% w / w, less than 15% w / w, less than 10% w / w, less than 5% w / w, or less than 3% w / w. In some embodiments, the amount of matrix may be greater than 1% w / w, greater than 3% w / w, greater than 5% w / w, greater than 10% w / w, greater than 15% w / w, greater than 20% w / w, or greater than 25% w / w.

[0040] In some embodiments, the amount of matrix forming agent in the matrix solution / suspension or pharmaceutical suspension may be about 0.1-10% w / w. In some embodiments, the amount of matrix forming agent in the matrix solution / suspension or pharmaceutical suspension may comprise 1.0-8.0% w / w or 2.0-5.0% w / w. In some embodiments, the amount of matrix in the matrix solution / suspension or pharmaceutical suspension may comprise more than 0.1% w / w, more than 0.5% w / w, more than 1.0% w / w, more than 2.0% w / w, more than 3.0% w / w, more than 4.0% w / w, more than 4.5% w / w, more than 5.0% w / w, or more than 8.0% w / w. In some embodiments, the amount of matrix forming agent in the matrix solution / suspension or pharmaceutical suspension may include less than 10% w / w, less than 8.0% w / w, less than 6.0% w / w, less than 5.0% w / w, less than 4.0% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, or less than 1.0% w / w. In some embodiments, the amount of matrix forming agent in the pharmaceutical composition may be about 3-15% w / w, about 4-10% w / w, or about 4-7% w / w. In some embodiments, the amount of matrix forming agent in the pharmaceutical composition may comprise greater than 0.1% w / w, greater than 0.5% w / w, greater than 1.0% w / w, greater than 2.0% w / w, greater than 3.0% w / w, greater than 4.0% w / w, greater than 5.0% w / w, greater than 6.0% w / w, greater than 7.0% w / w, greater than 8.0% w / w, greater than 9.0% w / w, greater than 10.0% w / w, greater than 11.0% w / w, greater than 12.0% w / w, greater than 13.0% w / w, or greater than 14.0% w / w. In some embodiments, the amount of matrix forming agent in the pharmaceutical composition may comprise less than 15% w / w, less than 14.0% w / w, less than 13.0% w / w, less than 12.0% w / w, less than 10.0% w / w, less than 9.0% w / w, less than 8% w / w, less than 7% w / w, less than 6% w / w, less than 5% w / w, or less than 4.0% w / w.

[0041] The structure-forming agent, or bulking agent, of the matrix may include a sugar. For example, suitable structure-forming agents include, but are not limited to, mannitol, dextrose, lactose, galactose, glycine, cyclodextrin, or combinations thereof. Structure-forming agents can be used as bulking agents in lyophilization because they crystallize to provide structural robustness to the lyophilized dosage form. In some embodiments, the amount of structure-forming agent in the matrix solution / suspension may be about 0.1-10% w / w. In some embodiments, the amount of structure-forming agent in the matrix solution / suspension or pharmaceutical suspension may include 1.0-8.0% w / w or 1.5-5.0% w / w. In some embodiments, the amount of structure-forming agent in the matrix solution / suspension or pharmaceutical suspension may comprise more than 0.1% w / w, more than 0.5% w / w, more than 1.0% w / w, more than 2.0% w / w, more than 3.0% w / w, more than 4.0% w / w, more than 4.0% w / w, more than 5.0% w / w, or more than 8.0% w / w. In some embodiments, the amount of structure-forming agent in the matrix solution / suspension or pharmaceutical suspension may comprise less than 10% w / w, less than 8.0% w / w, less than 6.0% w / w, less than 5.0% w / w, less than 4.0% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, or less than 1.0% w / w. In some embodiments, the amount of structure-forming agent in the pharmaceutical composition may be about 3-15% w / w, about 4-10% w / w, or about 4-7% w / w. In some embodiments, the amount of structure-forming agent in the pharmaceutical composition may include greater than 0.1% w / w, greater than 0.5% w / w, greater than 1.0% w / w, greater than 2.0% w / w, greater than 3.0% w / w, greater than 4.0% w / w, greater than 5.0% w / w, greater than 6.0% w / w, greater than 7.0% w / w, greater than 8.0% w / w, greater than 9.0% w / w, greater than 10.0% w / w, greater than 11.0% w / w, greater than 12.0% w / w, greater than 13.0% w / w, or greater than 14.0% w / w. In some embodiments, the amount of structure forming agent in the pharmaceutical composition may comprise less than 15% w / w, less than 14.0% w / w, less than 13.0% w / w, less than 12.0% w / w, less than 10.0% w / w, less than 9.0% w / w, less than 8% w / w, less than 7% w / w, less than 6% w / w, less than 5% w / w, or less than 4.0% w / w.

[0042] In some embodiments, the matrix solution / suspension and pharmaceutical suspension may include a viscosity modifier. For example, the viscosity modifier according to the embodiments provided herein may include a vegetable gum such as xanthan gum, arginine, guar gum, or locust gum, a protein such as collagen or gelatin, a sugar such as agar, carboxymethylcellulose, pectin, or carrageenan, a starch such as arrowroot, corn starch, dogtooth violet starch, potato starch, sago, or tapioca, and / or other suitable viscosity modifier. In some embodiments, the amount of viscosity modifier in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition may be 0-0.2% w / w or 0.01-0.1% w / w. In some embodiments, the amount of viscosity modifier in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition may be more than 0.01% w / w, more than 0.03% w / w, more than 0.05% w / w, more than 0.07% w / w, more than 0.1% w / w, more than 0.12% w / w, more than 0.15% w / w, or more than 0.17% w / w. In some embodiments, the amount of viscosity modifier in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition may be less than 0.2% w / w, less than 0.18% w / w, less than 0.15% w / w, less than 0.12% w / w, less than 0.1% w / w, less than 0.08% w / w, less than 0.06% w / w, or less than 0.03% w / w.

[0043] The solvent for the matrix solution / suspension and pharmaceutical suspension may be water, but the suspension may also include a co-solvent. In some embodiments, the solvent may be ethanol, alcohol, isopropanol, other lower alkanols, water (e.g., purified water), or a combination thereof. For example, a suitable solvent and / or co-solvent may be an alcohol, such as tert-butyl alcohol. In some embodiments, the remaining balance of the pharmaceutical suspension is solvent (i.e., QS100%).

[0044] The matrix solution / suspension and pharmaceutical suspension may also contain additional pharma- ceutically acceptable agents or excipients. Such additional pharma-ceutically acceptable agents or excipients include, but are not limited to, sugars, inorganic salts such as sodium chloride and aluminum silicate, modified starches, preservatives, antioxidants, viscosity enhancers, colorants, flavoring agents, pH adjusters, sweeteners, taste masking agents, and combinations thereof. Suitable colorants may include red, black, and yellow iron oxides, and FD&C dyes such as FD&C Blue No. 2 and FD&C Red No. 40, and combinations thereof. Suitable flavoring agents may include mint, raspberry, licorice, orange, lemon, grapefruit, caramel, vanilla, cherry, and grape flavors, and combinations thereof. Suitable pH adjusters may include citric acid, tartaric acid, phosphoric acid, hydrochloric acid, maleic acid, sodium hydroxide (e.g., 3% w / w sodium hydroxide solution), and combinations thereof. Suitable sweeteners may include aspartame, acesulfame K and thaumatin, and combinations thereof.Suitable taste-masking agents may include sodium bicarbonate, ion exchange resins, cyclodextrin-containing compounds, adsorbents or microencapsulated active agents, and combinations thereof.Those skilled in the art can easily determine the appropriate amounts of these various additional excipients, as needed.

[0045] Minimizing and / or preventing clumping of coating material in coated ibuprofen Described below are methods for preparing pharmaceutical compositions containing ibuprofen that minimize the amount of excess coating material and / or the amount of clumping of the excess coating material upon storage.

[0046] The method according to some embodiments includes removing excess coating material particles to minimize and / or prevent agglomeration of the coating material in the pharmaceutical product. In some embodiments, the method may include sieving the raw ibuprofen and / or coated ibuprofen. Specifically, the provided method may include sieving the ibuprofen and / or coated ibuprofen to remove any undesirable particles, such as excess coating material particles. The sieving process according to the disclosed embodiments may help prevent and / or minimize the possibility of agglomeration of the coating material, which may adversely affect the disintegration time and / or dissolution rate of the final product. The method may also include optimizing the coating and / or dosing ratio of the process.

[0047] The method for minimizing and / or preventing agglomeration of coating material particles according to the embodiments described herein may be applied to a dry, solvent-free mixing process for coating ibuprofen. Thus, the provided method is described below in the context of one or more dry, solvent-free mixing processes for coating ibuprofen. However, other variations of coating / encapsulation processes may also be used. For example, sugar coating, film coating, other variations of microencapsulation, compression coating, other variations of dry coating, melt coating, dip coating, rotary die coating, electrostatic coating, and / or other suitable types of coating may be used.

[0048] In general, the solvent-free mixing process for coating ibuprofen includes mixing a coating material with ibuprofen to produce coated ibuprofen. The coated ibuprofen is then mechanically and / or thermally stressed to deform the deformable coating material and create a continuous film surrounding the ibuprofen. The coated ibuprofen is then mixed with a matrix solution / suspension to form a pharmaceutical suspension. The pharmaceutical suspension containing the coated ibuprofen can be dispensed into a preformed mold, such as a blister pack, and further processed to produce a dispensable pharmaceutical composition (e.g., lyophilized agent, wafer, tablet, etc.).

[0049] However, when the final product (i.e., pharmaceutical composition) is stored, any excess coating material particles that are not bound to the coated ibuprofen may agglomerate. The amount and / or severity of agglomeration may increase over time. Agglomeration of excess coating material may increase the disintegration time and / or decrease the dissolution rate of the pharmaceutical product, and may adversely affect any functional properties of the coating material. Increased disintegration time may also cause unacceptable dispersion and mouthfeel characteristics in vivo.

[0050] Thus, it has been discovered that sieving the coated ibuprofen can remove excess coating material, thereby minimizing the amount of agglomeration of excess coating material during storage. Additionally, some embodiments include optimizing the coating ratio (amount of coating material relative to amount of uncoated ibuprofen), and optimizing the dosing ratio (amount of coated ibuprofen relative to the aqueous solution matrix containing all other inactive ingredients) can also minimize agglomeration of excess coating material particles.

[0051] The embodiments provided herein may be applied to coated ibuprofen produced using a dry, solvent-free process. Some mixing processes according to the embodiments described herein include coating ibuprofen with a taste-masking coating. Such coatings can control the disintegration time and / or dissolution rate of the orodispersible pharmaceutical composition such that the release of ibuprofen upon oral administration is delayed or significantly reduced during the first few minutes in the mouth, but a satisfactory amount of ibuprofen is released within 30 minutes of oral administration after swallowing. (For example, a satisfactory amount of ibuprofen may be 90% of the amount of ibuprofen released without the coating). U.S. Patent No. 9,107,851 ('851 Patent) is directed to an exemplary dry, solvent-free process for coating pharmaceutical ingredients and is incorporated herein in its entirety.

[0052] However, other variations of coating / encapsulation processes may also be used, for example sugar coating, film coating, other variations of microencapsulation, compression coating, other variations of dry coating, melt coating, dip coating, rotary die coating, electrostatic coating, and / or other suitable types of coating may be used.

[0053] Additionally, certain data provided herein relate to disintegration time. However, disintegration time is inversely proportional to dissolution rate. Thus, the data essentially also provides information regarding dissolution rate. Disintegration time may be measured according to the methodology established by the United States Pharmacopeia (Disintegration 701). In some embodiments, disintegration time may be 2-30 seconds or 5-20 seconds. In some embodiments, disintegration time may be less than 30 seconds, less than 25 seconds, less than 20 seconds, less than 15 seconds, less than 10 seconds, or less than 5 seconds. In some embodiments, disintegration time may be greater than 2 seconds, greater than 5 seconds, greater than 10 seconds, greater than 15 seconds, greater than 20 seconds, or greater than 25 seconds. Similarly, disintegration rate may be tested according to the methodology established by the United States Pharmacopeia (Disintegration 711).

[0054] In some embodiments, the raw ibuprofen can be sieved prior to the coating process to achieve a narrower particle size range. For example, the raw ibuprofen may be sieved to remove oversized particles and / or to remove undersized particles. In some embodiments, more than one mesh can be used to remove certain particles. For example, a sieving device may comprise a series of two or more meshes to remove particles of a certain size depending on the size of the mesh(es). The sieve can incorporate a vacuum transfer system to transport particles through the series of meshes of the device. Additionally, an ultrasonic probe can be incorporated into the sieving device to improve the flow of material during processing and minimize clogging of the meshes.

[0055] In some embodiments, the raw ibuprofen can be sieved using a mesh size of 30 μm to 500 μm, 50 μm to 450 μm, 100 μm to 400 μm, 150 μm to 350 μm, or 200 μm to 300 μm. In some embodiments, the raw ibuprofen can be sieved using a mesh size of less than 500 μm, less than 450 μm, less than 400 μm, less than 350 μm, less than 300 μm, less than 250 μm, less than 200 μm, less than 150, or less than 100 μm. In some embodiments, the raw ibuprofen can be sieved using a mesh size of more than 30 μm, more than 50 μm, more than 100 μm, more than 150 μm, more than 200 μm, more than 250 μm, more than 300 μm, more than 350 μm, or more than 400 μm.

[0056] Once the ibuprofen has been coated with the coating material to produce coated ibuprofen, the coated ibuprofen can be sieved to remove excess coating material and residual fine ibuprofen that is uncoated, partially coated, or coated. The excess coating material may include any coating material particles that are not bound to the coated ibuprofen. Upon storage of the final pharmaceutical product, any excess coating material may agglomerate. For example, fusion may occur between excess coating particles and coating particles that are already bound to the ibuprofen, preventing the disintegration of the unit or tablet or the ingress of media that would otherwise aid in the dissolution of the coated ibuprofen. Thus, agglomeration of excess coating material may cause an increase in disintegration time and / or a decrease in dissolution rate upon administration.

[0057] However, it has been determined that a method of sieving excess coating material from coated ibuprofen can minimize clumping of the coating material and maintain the initial disintegration time and / or dissolution rate of the final product. The sieving process can be either batch or continuous. Furthermore, this sieving process can be performed in addition to or instead of the sieving process performed on raw ibuprofen described above. In some embodiments, the parameters of the sieving process can be different between uncoated raw ibuprofen and coated ibuprofen.

[0058] In some embodiments, the coated ibuprofen can be sieved to remove coating material particles having an average particle size less than the average particle size of the desired coated ibuprofen. In some embodiments, more than one mesh can be used to remove certain particles. For example, the sieving device can include a series of two or more meshes to remove particles of a certain size depending on the size of the mesh(es). The sieve can incorporate a vacuum transfer system to deliver particles to the series of meshes of the device. Additionally, an ultrasonic probe can be incorporated into the sieving device to improve the flow of the material during processing and minimize clogging of the meshes. Flow aids (e.g., silica) may be included to facilitate movement through the sieve. For example, the coating material used to coat the ibuprofen may include a flow aid. Conversely, raw ibuprofen is non-cohesive and may not require the assistance of a flow aid during sieving. The sieving process may be a batch or continuous process.

[0059] In some embodiments, the raw ibuprofen can be sieved using a mesh size of 30 μm to 500 μm, 50 μm to 450 μm, 100 μm to 400 μm, 150 μm to 350 μm, or 200 μm to 300 μm. In some embodiments, the raw ibuprofen can be sieved using a mesh size of less than 500 μm, less than 450 μm, less than 400 μm, less than 350 μm, less than 300 μm, less than 250 μm, less than 200 μm, less than 150, or less than 100 μm. In some embodiments, the raw ibuprofen can be sieved using a mesh size of more than 30 μm, more than 50 μm, more than 100 μm, more than 150 μm, more than 200 μm, more than 250 μm, more than 300 μm, more than 350 μm, or more than 400 μm.

[0060] The coating ratio (i.e., amount of coating material relative to amount of uncoated ibuprofen) may be optimized to minimize and / or prevent excessive coating material clumping. For example, in some embodiments, the coating ratio may range from 5-85% or 10-50% w / w coating material to 15-95% or 50-90% w / w uncoated ibuprofen. In some embodiments, the amount of coating material may be less than 80% w / w, less than 70% w / w, less than 60% w / w, less than 50% w / w, less than 40% w / w, less than 30% w / w, less than 20% w / w, or less than 10% w / w. In some embodiments, the amount of coating material may be greater than 5% w / w, greater than 10% w / w, greater than 20% w / w, greater than 30% w / w, greater than 40% w / w, greater than 50% w / w, greater than 60% w / w, or greater than 70% w / w. In some embodiments, the amount of uncoated ibuprofen can be less than 95% w / w, less than 85% w / w, less than 75% w / w, less than 65% w / w, less than 55% w / w, less than 45% w / w, less than 35% w / w, or less than 25% w / w. In some embodiments, the amount of uncoated API can be greater than 20% w / w, greater than 30% w / w, greater than 40% w / w, greater than 50% w / w, greater than 60% w / w, greater than 70% w / w, greater than 80% w / w, or greater than 90% w / w.

[0061] The dosing ratio (i.e., the amount of coated ibuprofen relative to the amount of matrix solution / suspension containing all inactive ingredients) may be optimized to minimize and / or prevent excessive agglomeration of coating material. For example, in some embodiments, the dosing ratio may range from 5-60% w / w coated ibuprofen to 40-95% w / w matrix solvent / suspension. In some embodiments, the dosing ratio may include less than 60% w / w, less than 50% w / w, less than 40% w / w, less than 30% w / w, less than 20% w / w, or less than 10% w / w coated ibuprofen. In some embodiments, the dosing ratio may include more than 5% w / w, more than 10% w / w, more than 20% w / w, more than 30% w / w, more than 40% w / w, or more than 50% w / w coated ibuprofen. In some embodiments, the dosing ratio may comprise less than 95% w / w, less than 90% w / w, less than 80% w / w, less than 70% w / w, less than 60% w / w, or less than 50% w / w of the matrix solution / suspension. In some embodiments, the dosing ratio may comprise more than 40% w / w, more than 50% w / w, more than 60% w / w, more than 70% w / w, more than 80% w / w, or more than 90% w / w of the matrix solution / suspension.

[0062] Preserving functionally coated ibuprofen produced by a dry, solvent-free blending process and blended in suspension The pharmaceutical compositions and methods for preparing pharmaceutical compositions provided herein may include adding hydrophobic fumed silica during the coating process to provide a protective layer surrounding and / or partially or completely embedded within the functionally coated ibuprofen (or "first coating"). The addition of this hydrophobic fumed silica layer (or "second layer") can provide a protective layer to the functionally coated ibuprofen first coating layer and can minimize erosion of the first coating layer from the shear forces required to mix the functionally coated ibuprofen into the pharmaceutical suspension.

[0063] In general, the solvent-free mixing process for coating ibuprofen involves mixing a coating material with ibuprofen to produce functionally coated ibuprofen. The functionally coated ibuprofen is then mechanically and / or thermally stressed to deform the deformable coating material and create a continuous film surrounding the ibuprofen. The functionally coated ibuprofen is then mixed with a matrix solution or suspension to form a pharmaceutical suspension. The pharmaceutical suspension containing the functionally coated ibuprofen can be dispensed into a preformed mold, such as a blister pack, and further processed to produce a dispensable pharmaceutical composition (e.g., lyophilized, wafer, tablet, etc.). In some embodiments, the dispensable pharmaceutical composition can be an orodispersible product. Ideally, a minimal amount (if any) of the ibuprofen of the final dispensable pharmaceutical composition dissolves within the first few minutes of oral administration. This delayed or greatly reduced release of ibuprofen allows the orodispersible product to mask the taste of ibuprofen when in the patient's mouth. Alternatively, the ibuprofen can be released once the pharmaceutical composition has passed through the gastrointestinal tract.

[0064] However, when functionally coated ibuprofen is mixed into a matrix solution / suspension, the shear forces required to mix the particles into the matrix solution / suspension can erode the functional coating on the ibuprofen. Erosion of the coating can destroy or damage the properties of the functional coating. For example, erosion of the functional coating can destroy or damage any taste masking properties of the functional coating, allowing the ibuprofen to undergo dissolution in the oral cavity.

[0065] Thus, it has been discovered that hydrophobic fumed silica can be used not only as a flow aid for functionally coated ibuprofen to aid in downstream processing, but also to provide a hydrophobic barrier layer surrounding and / or partially or completely embedded within the functionally coated ibuprofen.Specifically, the hydrophobic barrier layer formed by hydrophobic fumed silica can protect one or more underlying coatings of the functionally coated ibuprofen during pharmaceutical suspension preparation and other downstream processing of the functionally coated ibuprofen.Thus, the ibuprofen according to some embodiments described herein may have a first functional coating and a second protective coating.

[0066] However, some pharmaceutical compositions and methods of preparing pharmaceutical compositions provided herein may include more than a first coating and a second coating. For example, some pharmaceutical compositions and methods of preparing same may include three, four, five, six, or more coatings. Thus, as used herein, the terms "first coating" and "second coating" should not be interpreted narrowly. As used herein, the term "first coating" refers to a functional coating of ibuprofen, and the term "second coating" refers to a protective coating including silica. In some embodiments, the functionally coated ibuprofen may have one or more coating layers between the "first coating" and the "second coating". In some embodiments, the functionally coated ibuprofen may have one or more coating layers between the ibuprofen and the "first coating". In some embodiments, the functionally coated ibuprofen may have one or more coating layers on the "second coating".

[0067] Once the functionally coated ibuprofen are prepared, they can be mixed into a matrix / suspension to form a pharmaceutical suspension for administration. Mixing the functionally coated ibuprofen into a matrix solution / suspension can erode the functional coating of the functionally coated ibuprofen. In some embodiments, to minimize this erosion, a hydrophobic fumed silica can be used to form a second coating layer that surrounds and / or is partially embedded and / or embedded in the functionally coated ibuprofen.

[0068] However, it is not naturally intuitive to coat the functionally coated ibuprofen (i.e., ibuprofen comprising at least a first coating, as described above) that is then mixed into a matrix solution / suspension with hydrophobic fumed silica. As described above, to create an orodispersible pharmaceutical composition according to an embodiment described herein, the functionally coated ibuprofen is mixed into a matrix solution / suspension comprising a matrix former, a structure former, and a solvent (often water) to form a pharmaceutical suspension. However, hydrophobic materials are naturally resistant to mixing into the matrix solution / suspension. Thus, it can be assumed that the hydrophobic fumed silica increases the interfacial tension between the functionally coated ibuprofen and the matrix solution / suspension, increasing the difficulty of incorporating the functionally coated ibuprofen into the matrix solution / suspension and potentially causing phase separation of the pharmaceutical suspension.

[0069] Interestingly, it has been determined that the first functional coating is preserved by using hydrophobic fumed silica to coat the functionally coated ibuprofen without substantially preventing the incorporation of the functionally coated ibuprofen into the matrix solution / suspension.As described above, the hydrophobic material in the matrix solution / suspension, for example, the functionally coated ibuprofen covered with hydrophobic fumed silica in the matrix solution / suspension, characteristically exhibits a relatively high surface tension between the hydrophobic material and the matrix solution / suspension.Therefore, it is believed that the surface tension between the hydrophobic functionally coated ibuprofen and the matrix solution / suspension is also relatively high.

[0070] However, as discussed below, the matrix solution / suspension may include a matrix-forming agent such as gelatin. Some matrix-forming agents, including gelatin, are mild surfactants, meaning that they can reduce the surface tension between the two materials. It is therefore believed that a matrix-forming agent that exhibits surfactant-like behavior can reduce the surface tension between the functionally coated ibuprofen and the matrix solution / suspension, thereby allowing the functionally coated ibuprofen to be incorporated into the matrix solution / suspension, while at the same time maintaining the protective properties of the hydrophobic fumed silica coating layer on the first functional coating of the functionally coated ibuprofen. This second coating layer, including hydrophobic fumed silica, can provide a hydrophobic barrier to the underlying first coating of the functionally coated ibuprofen to protect the underlying first coating from the shear forces required to mix the functionally coated ibuprofen into the pharmaceutical suspension. Coating the functionally coated ibuprofen with a hydrophobic barrier, including hydrophobic fumed silica, can protect the underlying (first) coating from erosion. Furthermore, the use of hydrophobic fumed silica according to the described method can prevent the matrix solution / suspension from penetrating through the coating to the ibuprofen.

[0071] Under normal processing conditions, without the hydrophobic fumed silica coating layer, the coating of the functionally coated ibuprofen may erode over time under the shear forces required to mix the functionally coated ibuprofen into the matrix solution / suspension. However, there may be a "processing window" of 2 hours or more from the time the functionally coated ibuprofen is first mixed into the matrix solution / suspension, during which the coating may remain intact and its functionality may remain intact. The exact time of this "processing window" may depend on the composition of the various components of the functionally coated ibuprofen, the composition of the matrix solution / suspension, the amount of materials used to prepare the coating of the functionally coated ibuprofen, and / or the physicochemical properties of the ibuprofen. However, if the functionally coated ibuprofen has a second coating that includes fumed silica, this "processing window" may be extended.

[0072] In some embodiments, the pharmaceutical composition or coated ibuprofen can comprise 0.5-35% w / w of hydrophobic fumed silica. In some embodiments, the pharmaceutical composition or coated ibuprofen can comprise 0.5-20% w / w, 0.5-10% w / w, or 0.5-5% w / w of hydrophobic fumed silica. In some embodiments, the pharmaceutical composition or coated ibuprofen can comprise more than 0.5% w / w, more than 1.0% w / w, more than 1.5% w / w, more than 2.0% w / w, more than 2.5% w / w, more than 3.0% w / w, more than 4.0% w / w, more than 5.0% w / w, more than 10% w / w, more than 15% w / w, more than 20% w / w, more than 25% w / w, or more than 30% w / w of hydrophobic fumed silica. In some embodiments, the pharmaceutical composition or coated ibuprofen can comprise less than 35% w / w, less than 25% w / w, less than 15% w / w, less than 10% w / w, less than 5.0% w / w, less than 4.0% w / w, less than 3.5% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, or less than 1.0% w / w of hydrophobic fumed silica. The hydrophobic fumed silica can be any of Aerosil R972 silica (Degussa), CAB-O-SIL EH-5 silica (Cabot), OX-50 silica (Degussa), COSM055 (Catalyst & Chemical Ind. Co. Ltd (Japan)), TS5 silica (Cabot), and / or other suitable types of silica.

[0073] The effectiveness of the protective layer comprising hydrophobic fumed silica can be determined by measuring the particle size of functionally coated ibuprofen in pharmaceutical suspension over time.If hydrophobic fumed silica is effective in preserving the coating, the particle size of functionally coated ibuprofen can remain constant or only slightly decrease over time.If it is not effective, the particle size of functionally coated ibuprofen can decrease more substantially over time.The particle size of functionally coated particles can be measured using laser diffraction, particle analyzer such as Malvern Mastersizer, or any other suitable means for analyzing particulates.

[0074] The effectiveness of the protective layer comprising hydrophobic fumed silica can also be measured by performing a dissolution test on the functionally coated ibuprofen. If the hydrophobic fumed silica is effective in preserving the coating, the release amount (e.g., percent release) of the functionally coated ibuprofen over time will be slower in the dissolution test. If it is not effective, the release amount of the functionally coated ibuprofen will be greater over time. The release amount of the functionally coated particles can be measured using a dissolution test, a spectrophotometric analyzer such as a Pion MicroDISS Profiler, or any other suitable means for performing a dissolution test.

[0075] Minimizing aeration of suspensions containing ibuprofen The embodiments provided herein may include adding a chemical compound, including terpenes and / or terpinol, to the matrix solution / suspension. Specifically, the pharmaceutical suspension embodiments provided herein may include a liquid flavor, including terpenes and / or terpinol. In some embodiments, the liquid flavor(s) may include the terpene limonene. The addition of certain chemical compounds, specifically liquid flavors including limonene, can minimize aeration of the suspension, increase the homogeneity of the suspension, and improve dose weight accuracy when the suspension is poured into a mold. As used herein, "dose weight accuracy" and related terms refer to the ability to accurately dispense a pharmaceutical suspension into a preformed mold. The accuracy of the dose weight of an administered pharmaceutical suspension may depend on several variables, including, but not limited to, uniformity, viscosity, chemical components, administration equipment, etc.

[0076] As mentioned above, conventional anti-aeration and / or mechanical means to minimize aeration have not been found to be successful due to the high viscosity of pharmaceutical suspensions. For example, when a vacuum is applied to a pharmaceutical suspension, the suspension height may increase because the viscous suspension "holds" the trapped air. Volatile formulation ingredients may also be lost during the vacuum process. Furthermore, conventional anti-aeration agents such as ethanol or simethicone emulsions are similarly ineffective in preventing suspension aeration.

[0077] Thus, it has been discovered that some chemical compounds, particularly liquid flavors containing terpenes such as limonene and / or terpinol, can minimize aeration of the pharmaceutical suspension when the hydrophobically coated ibuprofen is mixed into the matrix solution / suspension. By minimizing aeration, the hydrophobically coated ibuprofen is more efficiently and effectively dispersed throughout the pharmaceutical suspension. This increased dispersion can increase the homogeneity of the pharmaceutical suspension, dose weight accuracy, and content uniformity of the finished product.

[0078] As mentioned above, mixing hydrophobically coated ibuprofen into a matrix solution / suspension can generate air trapped in the liquid, or bubbles. Because coated ibuprofen is hydrophobic, it generally has a low affinity for the matrix solution / suspension. Therefore, instead of readily associating with and dispersing into the matrix solution / suspension, the hydrophobically coated ibuprofen preferably associates with the trapped air. In many fluids, the air bubbles typically migrate to the surface of the fluid and disappear into the air above. However, because hydrophobically coated ibuprofen has an affinity for the trapped air, the hydrophobically coated ibuprofen "holds" the air bubbles, thus preventing them from migrating to the surface and releasing into the air above the fluid. This causes the pharmaceutical suspension to be aerated. Aeration of the pharmaceutical suspension can cause phase separation and therefore a non-homogeneous suspension. Phase separation can also be exaggerated when exposed to shear forces introduced by a dosing pump. A non-homogeneous pharmaceutical suspension when passed through a dosing pump can cause the pump to seize, potentially leading to inaccurate dose weights, lack of uniformity across the finished product, and poor production efficiency due to stoppages.

[0079] Additionally, pharmaceutical suspensions containing hydrophobically coated ibuprofen may have high viscosity due to high loadings of hydrophobically coated ibuprofen (i.e., as much as 50% hydrophobically coated ibuprofen by weight). As noted above, entrapment of air in the pharmaceutical suspension during in-line mixing of the hydrophobically coated ibuprofen into the suspension may further increase the viscosity of the pharmaceutical suspension. Thus, phase separation and non-homogeneity of the suspension not only adversely affect dose weight accuracy and uniformity of the final product, but also adversely affect increased viscosity.

[0080] Interestingly, it has been found that certain chemical compounds can minimize the aeration of pharmaceutical suspensions containing hydrophobically coated ibuprofen when added to a matrix solution / suspension. In particular, according to some embodiments provided herein, chemical compounds containing terpenes and / or terpinol can minimize the amount of trapped air in pharmaceutical suspensions caused by in-line mixing of hydrophobically coated ibuprofen into a matrix solution / suspension. For example, even at relatively low concentrations, suspensions containing liquid flavors containing terpenes and / or terpinol can minimize the aeration of pharmaceutical suspensions. Specifically, it has been found that matrix solutions / suspensions containing one or more liquid flavors containing limonene can minimize the aeration in pharmaceutical suspensions during in-line mixing of hydrophobically coated ibuprofen. Other chemical compounds containing terpenes and terpinol have also been shown to be successful in minimizing the aeration of pharmaceutical suspensions. For example, chemical compounds containing terpenes such as limonene, carvone, humulene, taxadiene, and squalene may be suitable for minimizing the aeration of pharmaceutical suspensions. Terpinol may also be a suitable anti-aeration agent. In some embodiments, pure terpenes and / or pure terpinol may be used as anti-aeration agents. In some embodiments, liquid flavors containing terpenes and / or terpinol may be used as anti-aeration agents. In some embodiments, other suitable chemical compounds containing terpenes and / or terpinol may be used as anti-aeration agents.

[0081] One challenge posed by some chemical compounds containing terpenes and / or terpinols, such as some liquid flavors, is that they tend to be relatively oily. As with traditional oil and water, these oily chemical compounds may not be easily dispersed in a matrix solution / suspension. However, as discussed below, a matrix solution / suspension according to an embodiment herein may include gelatin as a matrix forming agent. Gelatin is inherently a mild surfactant. A surfactant may reduce the surface tension between two materials. Thus, in some embodiments, the gelatin of the matrix solution / suspension may reduce the surface tension between the oily chemical compounds and the matrix solution / suspension. This allows the oily chemical compounds, such as liquid flavors, to be properly incorporated into the matrix solution / suspension.

[0082] Under normal processing conditions, without the use of chemical compounds containing terpenes and / or terpinols, the coating of the hydrophobically coated ibuprofen will erode over time due to the shear forces required to mix the hydrophobically coated ibuprofen into a matrix solution / suspension to form a pharmaceutical suspension. However, there is a "processing window" of 2 hours or more during which the coating retains significant functionality. The exact time of this "processing window" varies from product to product and may depend on the composition of the components of the hydrophobically coated ibuprofen, the composition of the matrix solution / suspension, the amount of materials used to prepare the hydrophobically coated ibuprofen, the physicochemical properties of the ibuprofen, and / or the mixing conditions. Unfortunately, in the presence of chemical compounds containing terpenes and / or terpinols, this "processing window" may be significantly reduced due to interactions between these chemical compounds and the coating of the hydrophobically coated ibuprofen. These interactions may impair the functional properties of the coating. For example, interactions between liquid flavors and the coating of the hydrophobically coated ibuprofen may impair any taste masking function of the coating. However, it has been discovered that there is a threshold chemical compound (i.e., liquid flavor) concentration below which the chemical compound will not significantly impair the coating, but will not reduce the "processing window" so much that the coating of the hydrophobically coated ibuprofen is significantly eroded. Thus, this optimal amount of chemical compound, including terpenes and / or terpinols, sufficiently minimizes aeration of the pharmaceutical suspension, resulting in a homogenous pharmaceutical suspension that can be accurately dosed into molds to obtain a uniform end product.

[0083] Furthermore, chemical compounds containing terpenes and / or terpinol, and specifically liquid flavors containing limonene, have the potential to lower the freezing point of the pharmaceutical suspension, which may result in melting defects in the product further processed by freeze-drying. In particular, limonene has a freezing point of -74°C. However, no melting defects have been observed during the preparation of the disclosed products, and therefore, at least some chemical compounds containing terpenes and / or terpinol do not affect the pharmaceutical suspension, thereby adversely affecting the downstream freezing and freeze-drying process steps. The absence of melting defects under the current circumstances is believed to be due to the high solids content of the suspension, which helps to maintain the structure of the product, even in the presence of a freezing point depressant (i.e., limonene).

[0084] Matrix solution / suspension compositions according to embodiments described herein may include matrix forming agents, structure forming agents, anti-aeration agents, viscosity modifiers, and / or solvents.

[0085] In some embodiments, the amount of chemical compounds comprising terpenes and / or terpinols (i.e., anti-aeration agents) in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition can be 0.001-5.0% w / w. In some embodiments, the amount of chemical compounds comprising terpenes and / or terpinols (i.e., anti-aeration agents) in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition can be 1-5% w / w, 1-4% w / w, 1-3% w / w, 1-2% w / w, 0.05-3.0% w / w, 0.1-2.0% w / w, or 0.5-1.0% w / w. In some embodiments, greater than 0.001% w / w, greater than 0.01% w / w, greater than 0.05% w / w, greater than 0.1% w / w, greater than 0.3% w / w, greater than 0.5% w / w, greater than 0.8% w / w, greater than 1.0% w / w, greater than 1.5% w / w, greater than 2.0% w / w, greater than 2.5% w / w, greater than 3.0% w / w, greater than 3.5% w / w, greater than 4.0% w / w, or greater than 4.5% w / w of chemical compounds comprising terpenes and / or terpinols (i.e., anti-aeration agents) are present in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition. In some embodiments, less than 5.0% w / w, less than 4.5% w / w, less than 4.0% w / w, less than 3.5% w / w, less than 3.0% w / w, less than 2.5% w / w, less than 2.0% w / w, less than 1.5% w / w, less than 1.0% w / w, less than 0.8% w / w, less than 0.6% w / w, less than 0.3% w / w, or less than 0.1% w / w of chemical compounds comprising terpenes and / or terpinols (i.e., anti-aeration agents) are present in the matrix solution / suspension, pharmaceutical suspension, or pharmaceutical composition. In some embodiments, suitable anti-aeration agents may include orange flavor, strawberry flavor, mint flavor, raspberry flavor, licorice flavor, orange flavor, lemon flavor, lime flavor, grapefruit flavor, caramel flavor, vanilla flavor, cherry flavor, grape flavor, mixed fruit flavor, tutti frutti flavor, or any combination thereof.

[0086] Examples of minimizing clumping Several tests were performed to evaluate the effectiveness of removing excess coating material from coated ibuprofen by sieving and to optimize the coating ratio and dosing ratio. The disintegration time of pharmaceutical compositions containing various coated ibuprofen was measured under various conditions to study the effect of sieving excess coating material. It can be reasonably assumed that removing excess coating material can minimize coating material agglomeration. Optimizing the coating and dosing ratio can also help minimize coating material agglomeration. Minimizing the amount of agglomeration can then help maintain the desired disintegration time and / or dissolution rate of the pharmaceutical composition and coated ibuprofen. Thus, disintegration time is used as a metric to evaluate the amount of agglomeration in the following examples. In some embodiments, accelerated disintegration data at 50°C can indicate the presence of excess coating material that has not been sieved.

[0087] Additionally, coating ratio and dosing ratio information is provided for the following examples. Coating ratio refers to the amount of coating material relative to the amount of uncoated ibuprofen. Dosing ratio refers to the amount of coated ibuprofen relative to the matrix solution / suspension containing all inactive ingredients. EXAMPLES

[0088] Example 1: Ibuprofen was coated with carnauba wax at a coating ratio of 26:74. A dose ratio of 40:60 was used to produce freeze-dried tablets. Four separate batches of tablets were tested (batches 1-3 over 2 months and batch 4 over 6 months). These batches of tablets were tested at ICH (International Council for Harmonisation of Technical Requirements for Pharmaceuticals for Human Use) stability conditions of 25°C / 60% RH, 30°C / 65% RH, and 40°C / 75% RH, respectively, and sampled at 1 and 2 months for batches 1, 2, and 3. Additionally, each batch was exposed to stress conditions of 50°C to provide accelerated data at both 2 and 4 weeks for each study. Table 1 below provides disintegration time data for batches 1-3 of the 2-month study of coated ibuprofen. [Table 1]

[0089] The coated ibuprofen for batch 2 was poorly sieved after ibuprofen coating. Microscopic examination of the sieved coated ibuprofen (Figure 4B) indicated the presence of an excessive amount of unbound coating material. Microscopic examination of the sieved coated ibuprofen also indicated that the ibuprofen was poorly coated. As shown in the last column of Table 1, this batch exhibited a significantly longer disintegration time at 40°C / 75% RH stability test conditions after 2 months. (Initial disintegration time was less than 2 seconds, and disintegration time at 2 months was nearly 15 seconds). Thus, this result supports the hypothesis that the presence of an excessive amount of unbound coating material in the drug product causes an extension of disintegration time over time (as the drug product ages) due to agglomeration of the unbound coating material during storage.

[0090] Conversely, the coated ibuprofen for batch 3 was thoroughly sieved after ibuprofen coating. Microscopic examination of the sieved coated ibuprofen (FIG. 4C) indicated that the ibuprofen was thoroughly coated due to the absence of unbound coating material. The disintegration times of samples from this batch did not change significantly over the two month period for any of the ICH stability conditions. (Disintegration times throughout the two month study ranged from approximately 1 second to approximately 3 seconds). This supports the hypothesis that minimizing the presence of excess unbound coating material, for example by sieving, helps prevent clumping of the coating material in the drug product, especially when stored at elevated temperatures over time.

[0091] The coated ibuprofen for batch 1 was sieved after ibuprofen coating. Batch 1 showed similar disintegration times of less than 2 seconds compared to batches 2 and 3 for the initial time data points. However, after 2 months at 40C / 75% RH stability test conditions, the disintegration time increased to approximately 7 seconds or less. When stored at 50°C for 4 weeks, the disintegration time increased to approximately 10 seconds or less. This suggests that the sieving process for this batch did not adequately remove excess coating material, thus suggesting the presence of residual unbound coating material. Batch 2 experienced even more unbound coating material and a greater degree of agglomeration upon storage than that of batch 1. Microscopic examination of the sieved coated ibuprofen (Figure 4A) showed that the ibuprofen particles were reasonably well coated in the presence of residual unbound coating material.

[0092] Table 2 below shows the disintegration time data for the six month study of coated ibuprofen (ie, batch 4). [Table 2]

[0093] The coated ibuprofen for Batch 4 was sieved after coating the ibuprofen. Batch 4 in Table 2 showed little change in disintegration time over the 6 month study period. The initial disintegration time for Batch 4 was approximately 5 seconds, with the final disintegration time for the 25° C. / 60% RH sample being approximately 2 seconds, the 30° C. / 65% RH sample being approximately 2 seconds, and the 40° C. / 75% RH sample being approximately 2 seconds. However, an increase was observed upon storage at 50° C. As no increase was observed for tablets stored at temperatures below 40° C., this suggests that sieving removed most of the excess unbound coating material, but left enough residual material to clump together when the tablets were placed at 50° C. Microscopic examination (FIG. 4D) of the sieved coated ibuprofen showed that the ibuprofen was reasonably well coated in the presence of residual unbound coating material.

[0094] Example 2: Ibuprofen was coated with Sasol (synthetic) wax with a theoretical coating ratio of 26:74. The coated ibuprofen was sieved after coating. A 40:60 dose ratio was used to produce freeze-dried tablets and tested over a two-month period. The ibuprofen strength was 200mg. Each batch was tested at ICH stability conditions of 25°C / 60% RH, 30°C / 65% RH, and 40°C / 75% RH. Additionally, samples were exposed to stress conditions at 50°C to provide accelerated data at weeks 2 and 4 of the study. Table 3 below provides disintegration time data for the two-month study of coated ibuprofen with a 40:60 dose ratio. Microscopic examination of the sieved coated ibuprofen (Figure 4E) showed that the ibuprofen was reasonably well coated with a small amount of unbound coating material present. [Table 3]

[0095] Batch 5 in Table 3 shows no substantial change in disintegration time during the 2 month study or at the accelerated condition at 50°C. Specifically, the initial disintegration time for Batch 5 was approximately 3 seconds, and the disintegration time at 2 months was approximately 4 seconds for all three ICH stability conditions (25°C / 60% RH, 30°C / 65% RH, and 40°C / 75% RH). The disintegration time at 50°C accelerated condition at 2 weeks was approximately 3 seconds, and the disintegration time at 4 weeks was approximately 4 seconds. Based on the 50°C data, there may be a small residual amount of excess unbound coating material. If so, this small amount of excess unbound coating material does not cause a significant amount of clumping during storage, as the disintegration time does not increase significantly, if at all. This compares well with Batch 3 in Example 1, which used a different wax. These two examples demonstrate that clumping of coating material in a pharmaceutical product during storage can be minimized or prevented, especially at higher temperatures and during long storage periods, if excess unbound coating material is efficiently removed by sieving.

[0096] Example 3: Ibuprofen was coated with Sasol (synthetic) wax with a theoretical coating ratio of 26:74. After coating, the coated ibuprofen was then sieved. A 50:50 dose ratio was used to produce freeze-dried tablets and tested over a 3-month period. The ibuprofen strength was 200mg. As with Examples 1 and 2 above, each batch was tested at ICH stability conditions of 25°C / 60% RH, 30°C / 65% RH, and 40°C / 75% RH. Samples were also exposed to stress conditions at 50°C to provide accelerated data at 2 and 4 weeks during each study. Table 4 below provides data for a 3-month study of ibuprofen coated with 50:50 Sasol wax. Microscopic examination of the sieved coated API of batch 6 (Figure 4F) showed that the ibuprofen was well coated with some unbound coating material present. [Table 4]

[0097] Neither Batch 6 nor Batch 7 showed any significant change in disintegration time over the course of the three month study. Specifically, the initial disintegration time for Batch 6 samples was approximately 1 second, and the final three months at each of the three ICH stability conditions (25° C. / 60% RH, 30° C. / 65% RH, and 40° C. / 75% RH) were approximately 2 seconds. The disintegration times for Batch 6 at both the 2 week and 4 week accelerated 50° C. conditions were approximately 2 seconds.

[0098] The initial disintegration time for the batch 7 sample was approximately 2 seconds, and the final 3 month disintegration times at 25°C / 60% RH and 30°C / 65% RH ICH stability conditions were approximately 2 seconds. The final 3 month disintegration times at 40°C / 75% RH ICH stability conditions were approximately 3 seconds. The disintegration times at both the 2 week and 4 week accelerated 50°C conditions were approximately 5 seconds. The high coating ratio of 50:50 may increase the amount of excess unbound coating material if left unsieved. Although both batches used a higher dosing ratio of 50:50, which means a high loading of coated ibuprofen and any excess unbound coating material, these data infer that the sieving process of the coated ibuprofen was effective in removing excess unbound coating material to minimize agglomeration.

[0099] Example 4: Ibuprofen was coated with carnauba wax at theoretical coating ratios of 22.5:77.5 and 30:70. Using a dose ratio of 30:70, freeze-dried tablets were produced and studied over a two month period. The ibuprofen strength was 200 mg. The batches were stored in an oven at 40° C. The tablets were tested for disintegration time at initial, 25 days, and two months. Table 5 below provides the disintegration times for the study. Microscopic examination of unsieved coated ibuprofen (FIGS. 4G and 4H) and sieved coated ibuprofen (FIGS. 4I and 4J). The ibuprofen was well coated. There is no unbound coating material in the sieved sample. [Table 5]

[0100] Batches 8-11 show that the disintegration time of tablets stored at 40°C using a 30:70 dosing ratio for either unsieved (batches 8 and 10) or sieved (batches 9 and 11) coated ibuprofen does not increase over time. This supports the hypothesis that by reducing the dosing ratio, such as 30:70, the amount of excess unbound wax is sufficiently reduced to a level that can minimize clumping of excess unbound material when stored at higher temperatures over time.

[0101] A general summary of the results from the above examples is presented in Table 6. [Table 6A] [Table 6B]

[0102] Example of Functionally Coated Ibuprofen Preservation Example 5: A hydrophobic fumed silica was used to coat functionally coated ibuprofen according to embodiments described herein. Specifically, the hydrophobic fumed silica used was Aerosil R972 ("Aerosil"). Two different concentrations of Aerosil R972 were tested (1.5% w / w and 1.0% w / w). The size of the functionally coated ibuprofen was evaluated over a 6 hour holding period during which it was subjected to low shear mixing.

[0103] Figures 5, 6, and 7 provide an assessment of d10, d50, and d90 particle sizes, respectively, over a 6 hour period. Generally speaking, a particle size expressed in terms of its d10 means that 10% of the particles in a given amount of sample are less than the given particle size. Thus, a particle size expressed in terms of its d50 means that 50% of the particles in a given amount of sample are less than the given particle size, and a particle size expressed in terms of its d90 means that 90% of the particles in a given amount of sample are less than the given particle size.

[0104] As shown in Figure 5, the higher concentration of silica (1.5% w / w) was more effective at maintaining the original particle size, and therefore the coating, than the lower concentration of silica (1.0% w / w). Specifically, over a 6 hour period, the functionally coated ibuprofen with 1.5% w / w Aerosil lost approximately 30% of its original size, while the functionally coated ibuprofen with 1.0% w / w Aerosil lost approximately 80% of its original particle size.

[0105] Figure 6 also shows that a higher concentration of silica (1.5% w / w Aerosil) was more effective at maintaining the original functionally coated ibuprofen particle size, and therefore preserving the functional coating, than a lower concentration of silica (1.0% w / w Aerosil). Specifically, over a 6 hour period, the functionally coated ibuprofen with 1.5% w / w Aerosil lost nearly 20% of its original size, while the functionally coated ibuprofen with 1.0% w / w Aerosil lost approximately 45% of the original functionally coated API particle size.

[0106] 7 also shows that the higher concentration of silica (1.5% w / w Aerosil) was more effective at maintaining the original functionally coated ibuprofen particle size, and therefore preserving the functional coating of the functionally coated ibuprofen, than the lower concentration of silica (1.0% w / w Aerosil). Specifically, over a 6 hour period, the functionally coated ibuprofen with 1.5% w / w Aerosil lost nearly 15% of its original size, while the functionally coated ibuprofen with 1.0% w / w Aerosil lost approximately 35% of its original particle size.

[0107] Additionally, as the particle size of the functionally coated ibuprofen decreased, a distinct particle population containing particles between 5 μm and 20 μm in size appeared and increased over time. These particles are believed to be non-deformed coating material particles embedded within the deformed continuous coating material prior to erosion of the coating by shear forces. Thus, as the coating erodes and the particle size of the functionally coated ibuprofen decreases, the population size of these smaller particles increases as the deformed coating material surrounding them erodes, and these non-deformed particles are released from the functionally coated ibuprofen.

[0108] Overall, these studies suggest that coating functionally coated ibuprofen with 1.5% w / w Aerosil may increase the "processing window" to approximately 4 hours, instead of the 2 hour "processing window" that exists without silica. Within the first 4 hours of processing in suspension with a second outer coating containing 1.5% w / w Aerosil, the functionally coated ibuprofen shows little, if any, erosion of the coating.

[0109] Example 6: A hydrophobic fumed silica was used to coat the functionally coated ibuprofen according to the embodiments described herein. Specifically, the hydrophobic fumed silica used was Aerosil R972 ("Aerosil"). Five different concentrations of Aerosil R972 were tested: 0.0% w / w, 1.5% w / w, 2.5% w / w, 5.0% w / w, and 10.0% w / w. The release amount of the functionally coated ibuprofen was evaluated using a dissolution test (i.e., a dissolution medium of 0.01% SDS in phosphate buffer at pH 7.2, a medium temperature of 37°C, and a medium volume of 10 mL (ibuprofen)).

[0110] Figures 8 and 9 provide release assessments made over either a 5 minute or 30 minute period for functionally coated ibuprofen. Generally speaking, low volume dissolution results expressed in terms of % release mean that "x" percent of the weight of the added material dissolved in solution.

[0111] FIG. 8 shows the release data of ibuprofen coated with carnauba wax and various amounts of hydrophobic silica. As shown in the figure, higher concentrations of silica (up to 10.0% w / w) were more effective in providing slower release rates in the dissolution test and therefore maintaining the coating than lower concentrations of silica. Specifically, during the 5-minute test period, functionally coated ibuprofen with 10.0% w / w Aerosil (i.e., ibuprofen coated with carnauba wax) showed a 1.5% release after 5 minutes, while functionally coated ibuprofen with 0.0% w / w Aerosil showed a 24.9% release. Functionally coated ibuprofen with intermediate levels of Aerosil (i.e., 1.5% w / w, 2.5% w / w, and 5.0% w / w) showed dissolution results after 5 minutes of 12.1%, 7.4%, and 2.3%, respectively.

[0112] FIG. 9 provides release data for ibuprofen coated with Sasol (synthetic) wax and various levels of hydrophobic silica. FIG. 10 also shows that higher concentrations of silica (up to 10.0% w / w) were more effective in providing slower release rates in the dissolution test and therefore maintaining the coating than lower concentrations of silica. Specifically, during the 5 minute test period, functionally coated ibuprofen with 10.0% w / w Aerosil (i.e., ibuprofen coated with synthetic wax) showed 2.8% release after 5 minutes, while functionally coated ibuprofen with 0.0% w / w Aerosil showed 8.5% release. Functionally coated ibuprofen with intermediate levels of Aerosil (i.e., 1.5% w / w, 2.5% w / w, and 5.0% w / w) showed 5 minute dissolution results of 4.3%, 3.6%, and 2.4% released, respectively.

[0113] Examples of minimizing drafts The effectiveness of the chemical compound, including terpenes and / or terpinols, in minimizing aeration can be determined in part by measuring the particle size of the hydrophobically coated ibuprofen in the pharmaceutical suspension over time. If the chemical compound is effective, the aeration of the suspension will be low enough that the particle size of the hydrophobically coated ibuprofen will remain constant or will not decrease significantly over time. If it is not effective, the aeration of the suspension will be higher than desired and the particle size of the hydrophobically coated ibuprofen may decrease more substantially over time. The degree of aeration of the suspension is evaluated by measuring the foam height in the mixing vessel. The particle size of the functionally coated particles can be measured using laser diffraction, a particle analyzer such as a Malvern Mastersizer, or any other suitable means for analyzing particulates.

[0114] Example 7: A series of suspension mixtures were made by mixing coated ibuprofen in matrix solutions / suspensions containing various levels of limonene, orange flavor, and strawberry flavor. The foam heights from these suspensions are summarized in Tables 7, 8, and 9, respectively. [Table 7] [Table 8] [Table 9]

[0115] The results in Tables 7 and 8 show that the addition of limonene and orange flavor at levels of 0.15% w / w and above minimized aeration. Strawberry (Table 9) also reduced aeration, but not to the same extent.

[0116] Example 8: Figures 10, 11, and 12 show the reduction in particle size (d10, d50, and d90, respectively) of hydrophobically coated ibuprofen in pharmaceutical suspensions containing various concentrations of liquid orange flavor. A particle size expressed in terms of its d10 means that 10% of the particles in a given amount of sample are below the given particle size. Thus, the d50 particle size represents 50 percent of the particles in a given amount of sample are below the given particle size, and the d90 particle size represents 90 percent of the particles in a given amount of sample are below the given particle size. Specifically, Figures 3-5 show the results of testing suspension formulations containing hydrophobically coated ibuprofen and liquid orange flavor at concentrations including 0.0%, 0.15%, 0.45%, and 0.60% w / w, held for up to 6 hours with low shear mixing.

[0117] At concentrations of up to 0.45% w / w orange flavor (including 0.15% w / w), the reduction in d10, d50, and d90 particle size within the first 2 hours "processing window" is nearly similar to that of the pharmaceutical suspension containing hydrophobically coated ibuprofen without any liquid flavor (0% liquid flavor). However, at a concentration of 0.6% w / w liquid orange flavor, the coating of the hydrophobically coated ibuprofen is easily removed and a rapid reduction in particle size is observed. Furthermore, at a concentration of 0.3% w / w liquid orange flavor, the aeration of the suspension is low enough that there is little, if any, damage to the coating of the coated ibuprofen and only a minimal reduction in the particle size of the hydrophobically coated ibuprofen.

[0118] Example 9: Figures 13, 14, and 15 provide data on the reduction of d10, d50, and d90 particle size of hydrophobically coated ibuprofen, respectively, for a specific component, limonene, found in several liquid flavors. These tests were performed to explore the behavior of a specific component, limonene, of liquid flavors, relative to hydrophobically coated ibuprofen in suspension. Note that the concentrations of limonene shown in the figures are significantly higher than the concentrations of limonene that would be present if liquid flavors were used. In Figures 13-15, pure limonene was used at concentrations of 0.25% w / w, 0.45% w / w, and 0.75% w / w and tested over a 24 hour period. As shown in all three figures, the 0.25% w / w limonene concentration had a much less detrimental effect on the coating of hydrophobically coated ibuprofen particle size than the 0.45% w / w and 0.75% w / w limonene concentrations. Additionally, pharmaceutical suspensions tested with 0.25% w / w limonene contained sufficiently low amounts of aeration that these studies therefore confirm that the limonene in the liquid orange flavor tested in Figures 3-5 is at least partially responsible for minimizing aeration of the pharmaceutical suspensions and subsequently eroding the coating of the hydrophobically coated ibuprofen at relatively high amounts and / or relatively high exposure times.

[0119] Example 10: Figure 16 shows the test data for two different liquid flavors (strawberry and orange). The d10, d50, and d90 particle sizes of hydrophobically coated ibuprofen were tested for both strawberry and orange liquid flavors. Both strawberry and orange liquid flavors contain limonene. As shown in the figure, both flavors behave similarly with respect to hydrophobically coated ibuprofen particle size. The d10 particle size sample showed a greater amount of particle size reduction within the first two hours of testing than the d50 and d90 particle size samples. The d50 and d90 particle size samples showed less particle size reduction within the same two hours. However, this observation is consistent with the d10, d50, and d90 particle size data of the examples discussed above.

[0120] Additionally, in all studies, as the particle size of the hydrophobically coated API (ibuprofen) particles decreases, a distinct particle population comprising particles between 5 μm and 20 μm in size was observed to appear and increase over time. These particles are believed to be non-deformed coating material particles embedded within the continuous coating material that was deformed by shear forces prior to coating erosion. Thus, as the coating erodes and the particle size of the hydrophobically coated ibuprofen decreases, the population size of these smaller particles increases as the deformed coating material surrounding them erodes, and these non-deformed particles are released from the hydrophobically coated ibuprofen.

[0121] Overall, these studies demonstrate that optimizing the amount of terpene limonene added to a pharmaceutical suspension containing hydrophobically coated ibuprofen minimizes the amount of aeration in the suspension to allow for downstream processing while not adversely affecting the coating of the hydrophobically coated ibuprofen (as determined by the particle size of the hydrophobically coated ibuprofen).

[0122] The foregoing description has been set forth in terms of specific embodiments for purposes of illustration. However, the illustrative discussion above is not intended to be exhaustive or to limit the invention to the precise forms disclosed. Many modifications and variations are possible in light of the above teachings. The embodiments were chosen and described in order to best explain the principles of the techniques and their practical application. In order to enable those skilled in the art to optimally utilize the techniques and various embodiments, with various modifications suited to the particular use contemplated.

[0123] Although the present disclosure and embodiments have been fully described with reference to the accompanying drawings, it should be noted that various changes and modifications will become apparent to those skilled in the art, and such changes and modifications should be understood to be included within the scope of the present disclosure and embodiments as defined by the appended claims.

Claims

1. 65-85% w / w of ibuprofen; a coating material for coating said ibuprofen at 15-30% w / w; a matrix surrounding said ibuprofen at 3-15% w / w.

2. 10. The pharmaceutical composition of claim 1 comprising 50 to 400 mg of ibuprofen.

3. 2. The pharmaceutical composition of claim 1, wherein the coating material comprises a first coating material and a second coating material, and the pharmaceutical composition comprises 10-30% w / w of the first coating material and 0.5-10% w / w of the second coating material.

4. The pharmaceutical composition of claim 3 , wherein the first coating material comprises a wax.

5. The pharmaceutical composition of claim 4 , wherein the second coating material comprises silica.

6. 10. The pharmaceutical composition of claim 1, comprising 1-5% w / w of an anti-aerator.

7. 5. The pharmaceutical composition of claim 4, wherein the first coating material comprises one or more of carnauba wax, synthetic wax, or candelilla wax.

8. The pharmaceutical composition of claim 1 , wherein the matrix comprises a matrix-forming agent and a structure-forming agent.

9. 9. The pharmaceutical composition of claim 8, wherein the matrix forming agent comprises one or more of a water soluble material, a water dispersible material, a polypeptide, a polysaccharide, polyvinyl alcohol, polyvinylpyrrolidone, and acacia.

10. The pharmaceutical composition of claim 8 , wherein the matrix-forming agent comprises a polypeptide.

11. The pharmaceutical composition of claim 10 , wherein the polypeptide comprises gelatin.

12. 9. The pharmaceutical composition of claim 8, wherein the structure-forming agent comprises one or more of mannitol, dextrose, lactose, galactose, and cyclodextrin.

13. 9. The pharmaceutical composition of claim 8, wherein the structure-forming agent comprises mannitol.

14. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 1 month.

15. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

16. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 3 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

17. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30°C and at least 65% relative humidity for at least 1 month.

18. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30°C and at least 65% relative humidity for at least 2 months.

19. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 1 month.

20. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 2 months.

21. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 3 months.

22. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30°C and at least 65% relative humidity for at least 3 months.

23. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 3 months.

24. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 6 months.

25. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30°C and at least 65% relative humidity for at least 6 months.

26. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 6 months.

27. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a dissolution test result of 10% or less after 5 minutes.

28. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a dissolution test result of 5% or less after 5 minutes.

29. 10. The pharmaceutical composition of claim 1, wherein the pharmaceutical composition has a dissolution test result of 3% or less after 5 minutes.

30. The pharmaceutical composition of claim 1 , wherein the matrix comprises a viscosity modifier.

31. 31. The pharmaceutical composition of claim 30, wherein the viscosity modifier comprises xanthan gum.

32. 7. The pharmaceutical composition of claim 6, wherein the anti-aerating agent comprises one or more of a terpene or a terpinol.

33. 7. The pharmaceutical composition of claim 6, wherein the anti-aeration agent comprises a liquid flavor.

34. 7. The pharmaceutical composition of claim 6, wherein the anti-aeration agent comprises a liquid flavor comprising limonene.

35. 7. The pharmaceutical composition of claim 6, wherein the anti-aeration agent comprises one or more of an orange flavor, a lemon flavor, a grapefruit flavor, a lime flavor, a strawberry flavor, or a peppermint flavor.

36. The pharmaceutical composition of claim 8, wherein the pharmaceutical composition comprises 3-10% w / w of a matrix forming agent.

37. 9. The pharmaceutical composition of claim 8, wherein the pharmaceutical composition comprises 3-10% w / w of a structure-forming agent.

38. coating the ibuprofen with a first coating material to form a coated ibuprofen, the first coating material comprising one or more deformable components; applying a mechanical stress to the coated ibuprofen to deform the one or more deformable components; coating the coated ibuprofen with a second coating material comprising silica; applying a mechanical stress to embed the second coating material into the first coating material of the coated ibuprofen; sieving the coated ibuprofen to remove excess first coating material, the excess first coating material comprising first coating material that is not bound to the coated ibuprofen; forming a pharmaceutical suspension comprising twice-coated ibuprofen and a matrix solution or suspension; administering the pharmaceutical suspension into a mold; and freeze-drying the administered pharmaceutical suspension in a mold to form a pharmaceutical composition.

39. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition comprises 50 to 400 mg of ibuprofen.

40. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition comprises 65-85% w / w ibuprofen.

41. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition comprises 15-30% w / w of the first and second coating materials.

42. 39. The pharmaceutical composition of claim 38, wherein the first coating material is configured to mask the taste of ibuprofen.

43. 39. The pharmaceutical composition of claim 38, wherein the silica comprises hydrophobic fumed silica.

44. 40. The pharmaceutical composition of claim 38, wherein the matrix solution or suspension comprises an anti-aeration agent.

45. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition comprises 3-15% w / w matrix.

46. 39. The pharmaceutical composition of claim 38, comprising sieving uncoated ibuprofen.

47. 39. The pharmaceutical composition of claim 38, wherein sieving the coated ibuprofen comprises passing the coated ibuprofen through a device comprising two or more sieves.

48. 39. The pharmaceutical composition of claim 38, wherein sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 75 μm or greater.

49. 39. The pharmaceutical composition of claim 38, wherein sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 200 μm or less.

50. 40. The pharmaceutical composition of claim 38, wherein the first coating material comprises a wax.

51. 51. The pharmaceutical composition of claim 50, wherein the wax comprises one or more of carnauba wax, candelilla wax, or a synthetic wax.

52. 39. The pharmaceutical composition of claim 38, wherein the matrix solution or suspension comprises a matrix-forming agent and a structure-forming agent.

53. 53. The pharmaceutical composition of claim 52, wherein the matrix forming agent comprises one or more of a water soluble material, a water dispersible material, a polypeptide, a polysaccharide, polyvinyl alcohol, polyvinylpyrrolidone, and acacia.

54. 53. The pharmaceutical composition of claim 52, wherein the matrix forming agent comprises a polypeptide.

55. 55. The pharmaceutical composition of claim 54, wherein the polypeptide comprises gelatin.

56. 53. The pharmaceutical composition of claim 52, wherein the structure-forming agent comprises one or more of mannitol, dextrose, lactose, galactose, and cyclodextrin.

57. 53. The pharmaceutical composition of claim 52, wherein the structure-forming agent comprises mannitol.

58. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition comprises a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 1 month.

59. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

60. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 3 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

61. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 1 month.

62. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 2 months.

63. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 1 month under storage conditions of at least 40°C and at least 75% relative humidity.

64. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 2 months.

65. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 3 months.

66. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 3 months.

67. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40° C. and at least 75% relative humidity for at least 3 months.

68. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 6 months.

69. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 6 months.

70. 39. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40°C and at least 75% relative humidity for at least 6 months.

71. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a dissolution test result of 10% or less after 5 minutes.

72. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a dissolution test result of 5% or less after 5 minutes.

73. 40. The pharmaceutical composition of claim 38, wherein the pharmaceutical composition has a dissolution test result of 3% or less after 5 minutes.

74. 40. The pharmaceutical composition of claim 38, wherein the weight of the administered pharmaceutical suspension is within 10 percent of a target weight.

75. 40. The pharmaceutical composition of claim 38, wherein the weight of the administered pharmaceutical suspension is within 5 percent of a set target weight.

76. 40. The pharmaceutical composition of claim 38, wherein the matrix solution or suspension comprises a viscosity modifying agent.

77. 77. The pharmaceutical composition of claim 76, wherein the viscosity modifying agent comprises xanthan gum.

78. 39. The pharmaceutical composition of claim 38, wherein mixing the coated ibuprofen into a matrix solution or suspension comprises in-line mixing at 15-20 degrees Celsius.

79. 45. The pharmaceutical composition of claim 44, wherein the anti-aerating agent comprises one or more of a terpene or a terpinol.

80. 45. The pharmaceutical composition of claim 44, wherein the anti-aeration agent comprises a liquid flavor.

81. 45. The pharmaceutical composition of claim 44, wherein the anti-aeration agent comprises a liquid flavor comprising limonene.

82. 45. The pharmaceutical composition of claim 44, wherein the anti-aerators comprise one or more of an orange flavor, a lemon flavor, a grapefruit flavor, a lime flavor, a strawberry flavor, or a peppermint flavor.

83. 45. The pharmaceutical composition of claim 44, wherein the pharmaceutical composition comprises 1-5% w / w of an anti-aerator.

84. 40. The pharmaceutical composition of claim 38, wherein the coated ibuprofen experiences less than 40% loss in particle size within the first 2 hours after being mixed into the solution matrix.

85. 40. The pharmaceutical composition of claim 38, wherein the coated ibuprofen experiences less than 30% loss in particle size within the first 2 hours after being mixed into the solution matrix.

86. 39. The pharmaceutical composition of claim 38, wherein the coated ibuprofen experiences less than a 20% loss in particle size within the first 2 hours after being mixed into the solution matrix.

87. A method of treating a patient comprising administering to the patient a pharmaceutical composition according to any one of claims 38 to 86.

88. 88. The method of claim 87, wherein the patient is a human.

89. 1. A method for preparing a pharmaceutical composition comprising the steps of: coating ibuprofen with a first coating material to form a coated ibuprofen, said first coating material including one or more deformable components; applying a mechanical stress to the coated ibuprofen to deform the one or more deformable components; coating the coated ibuprofen with a second coating material comprising silica; applying a mechanical stress to embed the second coating material into the first coating material of the coated ibuprofen; sieving the coated ibuprofen to remove excess first coating material, the excess first coating material comprising first coating material that is not bound to the coated ibuprofen; forming a pharmaceutical suspension comprising the twice-coated ibuprofen and a matrix solution or suspension; administering the pharmaceutical suspension into a mold; and freeze-drying the administered pharmaceutical suspension in a mold to form a pharmaceutical composition.

90. 90. The method of claim 89, wherein the pharmaceutical composition comprises 50 to 400 mg of ibuprofen.

91. 90. The method of claim 89, wherein the pharmaceutical composition comprises 65-85% w / w ibuprofen.

92. 90. The method of claim 89, wherein the pharmaceutical composition comprises 15-30% w / w of the first and second coating materials.

93. 90. The method of claim 89, wherein the pharmaceutical composition comprises 3-15% w / w matrix.

94. 90. The method of claim 89, comprising sieving the uncoated ibuprofen.

95. 90. The method of claim 89, wherein the first coating material is configured to mask the taste of the ibuprofen.

96. 90. The method of claim 89, comprising administering the suspension into a preformed mold.

97. 90. The method of claim 89, wherein the silica comprises hydrophobic fumed silica.

98. 90. The method of claim 89, wherein sieving the coated ibuprofen comprises passing the coated ibuprofen through a device comprising two or more sieves.

99. 90. The method of claim 89, wherein sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 75 μm or greater.

100. 90. The method of claim 89, wherein sieving the coated ibuprofen comprises sieving the coated ibuprofen to an average particle size of 200 μm or less.

101. 90. The method of claim 89, wherein the first coating material comprises a wax.

102. 90. The method of claim 89, wherein the first coating material comprises one or more of carnauba wax, candelilla wax, or synthetic wax.

103. 90. The method of claim 89, wherein the matrix solution or suspension comprises a matrix-forming agent and a structure-forming agent.

104. 104. The method of claim 103, wherein the matrix forming agent comprises one or more of a water soluble material, a water dispersible material, a polypeptide, a polysaccharide, a polyvinyl alcohol, a polyvinylpyrrolidone, and acacia.

105. The method of claim 103, wherein the matrix forming agent comprises a polypeptide.

106. 106. The method of claim 105, wherein the polypeptide comprises gelatin.

107. 104. The method of claim 103, wherein the structure-forming agent comprises one or more of mannitol, dextrose, lactose, galactose, and cyclodextrin.

108. 104. The method of claim 103, wherein the structure-forming agent comprises mannitol.

109. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

110. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 3 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 2 months.

111. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 1 month under storage conditions of at least 30° C. and at least 65% relative humidity.

112. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 2 months.

113. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 1 month under storage conditions of at least 40° C. and at least 75% relative humidity.

114. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40° C. and at least 75% relative humidity for at least 2 months.

115. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 3 months.

116. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 3 months.

117. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40° C. and at least 75% relative humidity for at least 3 months.

118. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 25°C and at least 60% relative humidity for at least 6 months.

119. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 30° C. and at least 65% relative humidity for at least 6 months.

120. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less under storage conditions of at least 40° C. and at least 75% relative humidity for at least 6 months.

121. 90. The method of claim 89, wherein the pharmaceutical composition has a disintegration time of 4 seconds or less for at least 1 month under storage conditions of at least 25°C and at least 60% relative humidity.

122. 90. The method of claim 89, wherein the matrix solution or suspension comprises an anti-aeration agent.

123. 90. The method of claim 89, wherein the pharmaceutical composition has a dissolution test result of 10% or less after 5 minutes.

124. 90. The method of claim 89, wherein the pharmaceutical composition has a dissolution test result of 5% or less after 5 minutes.

125. 90. The method of claim 89, wherein the pharmaceutical composition has a dissolution test result of 3% or less after 5 minutes.

126. 90. The method of claim 89, wherein the weight of the administered pharmaceutical suspension is within 10 percent of a target weight.

127. 90. The method of claim 89, wherein the weight of the administered pharmaceutical suspension is within 5 percent of a target weight.

128. 90. The method of claim 89, wherein the matrix solution or suspension comprises a viscosity modifier.

129. 129. The method of claim 128, wherein the viscosity modifier comprises xanthan gum.

130. 90. The method of claim 89, wherein mixing the coated ibuprofen into a matrix solution or suspension comprises in-line mixing at 15-20 degrees Celsius.

131. 123. The method of claim 122, wherein the anti-aeration agent comprises one or more of a terpene or a terpinol.

132. 123. The method of claim 122, wherein the anti-venting agent comprises a liquid flavor.

133. 123. The method of claim 122, wherein the anti-venting agent comprises a liquid flavor comprising limonene.

134. 123. The method of claim 122, wherein the anti-ventilation agent comprises one or more of an orange flavor, a lemon flavor, a grapefruit flavor, a lime flavor, a strawberry flavor, or a peppermint flavor.

135. 90. The method of claim 89, wherein the pharmaceutical composition comprises 3-10% w / w of a matrix forming agent.

136. 90. The method of claim 89, wherein the pharmaceutical composition comprises 3-10% w / w of a structure-forming agent.

137. 90. The method of claim 89, wherein the coated ibuprofen experiences less than 40% loss in particle size within the first 2 hours after being mixed into the solution matrix.

138. 90. The method of claim 89, wherein the coated ibuprofen experiences less than 30% loss in particle size within the first 2 hours after being mixed into the solution matrix.

139. 90. The method of claim 89, wherein the coated ibuprofen experiences less than 20% loss in particle size within the first 2 hours after being mixed into the solution matrix.

Citation Information

Patent Citations

  • Solvent-free mixing method for coating pharmaceutical components

    JP2015533162A